Solid Dispersion-Based Compression-Coated Tablets of Efonidipine Hydrochloride Ethanolate: Enhancing Dissolution and Achieving Delayed Intestinal Release - Shivani Chauhan; Kiran Dudhat; Sunny Shah; Chetan Borkhataria; Trupesh Pethani; Dhruvi Patel; Bhoomika Chaturvedi; Bhusan Patil; Mitava Patel; Dhaval Mori (Journal of Pharmaceutical Innovation, 2027)

Disparities in Gallbladder Cancer: Epidemiology, Molecular Mechanisms, and Clinical Implications - Om Saswat Sahoo; Gurpeet Singh Gill; Arnab Nayek; Nidhi Bhardwaj; Kailash Chand Kurdia; Saurabh Galodha; R Chetan; Ruby Dhar; Subhradip Karmakar (Molecular Biology Reports, 2026)

Indazole-Based Small Molecules as Cyclin-Dependent Kinase-2 Inhibitors: Synthesis, In Vitro Anticancer Evaluation, and Molecular Docking Studies - Vinod Ashtekar; Ashish Patel; Drashti Shah; Ranjitsinh C. Dabhi; Chetan B. Sangani; Nishith Teraiya; Arjun S. Chaudhari; Vatsal Chaudhari; Hemant N. Patel (Journal of Pharmaceutical Innovation, 2026)

Wind–vehicle–bridge interaction and driving safety reliability under skew winds - Alfredo Camara; Chetan Jagadeesh; Sam Divall (Engineering Structures, 2026)

Controlled Drug Delivery of Tenoxicam and Flufenamic Acid Via Transdermal Patches: A DOE Optimization Study - Payal N. Vaja; Hardik L. Varu; Chetan H. Borkhataria; Chetankumar B. Rathod (Journal of Pharmaceutical Innovation, 2026)

Advancements in green click chemistry: Sustainable catalytic methods for the synthesis of 1,2,3-triazole derivatives - Sahil Jindal; Rakesh Kumar; Chetan Sharma; Man Vir Singh; Amit kumar; Yogesh Kumar (Next Research, 2026)

The modelled impact of low traffic neighbourhoods (LTNs) on air pollution: findings from 5 schemes in London - Haneen Khreis; Matthew Williams; Chetan Lad; Dave Fevyer; Anthony A. Laverty; David Jinks; Jamie Furlong; James Woodcock; Phil Edwards; Anna Goodman (Environmental Research, 2026)

Ultrasound-assisted alkaline extraction of pearl millet protein: Characterization of physical, structural, thermal, and techno-functional properties - Upendra Singh; Raj Kumar Duary; Sunil Meena; Kappat Valiyapeediyekkal Sunooj; Kamalesh Kumar Meena; Chetan Prakash Yadav (Bioresource Technology Reports, 2026)

Integrative Pathometric and Molecular Analysis to Characterize Slow Disease Development in Blackgram Germplasm Against Erysiphe polygoni - V. Vasanthi; P. Kishore Varma; M. Suresh; N. Kamakshi; Ch. Rani; D. Ramesh; V. Prasanna Kumari; K. K. Chetan (Plant Molecular Biology Reporter, 2026)

Development and evaluation of hydrogel microneedles based on Gantrez® S-97 and hyaluronic acid for transdermal delivery of metoclopramide - Maitri Chetan Trivedi; Ariana Radmard; Ajay K. Banga (Drug Delivery and Translational Research, 2026)
Microneedles have emerged as a promising technology for enhancing transdermal delivery. The micron-sized needles penetrate the stratum corneum with minimal pain and discomfort. Among the different microneedle types, hydrogel microneedles offer distinct advantages, including sustained drug release and biocompatibility. The present study aimed to optimize the formulation of hydrogel microneedles composed of Gantrez ® S-97, a hydrophilic polymer, crosslinked with the sodium salt of hyaluronic acid at 80 °C to form a hydrogel matrix. Polyvinyl pyrrolidone, a synthetic water-soluble polymer, was incorporated to improve microneedles stability and enhance sustained drug release. Metoclopramide hydrochloride is a dopamine receptor antagonist with variable oral bioavailability and established clinical use in the management of chemotherapy-induced nausea, vomiting, and gastroesophageal reflux disorders. Metoclopramide-loaded hydrogel microneedle formulations were prepared with varying polymer compositions and evaluated by in vitro permeation studies. The optimized formulation demonstrated mechanical strength, uniform needle morphology, and a sustained drug release profile over 24 h. The hydrogel microneedles achieved up to an 18-fold enhancement in transdermal drug permeation compared to a conventional transdermal film.

LC-MS/MS-based discovery of new cytochalasin from fungus Rosellinia sanctae-cruciana - Nisha Sharma; Poonam Choudhary; Priya Kumari; Mohd Murtaza; Vidushi Abrol; Chetan Kumar; Rohit Singh; Sundeep Jaglan; Manoj Kushwaha (Natural Product Research, 2026)

Retraction notice to “Use of biomass-derived biochar in wastewater treatment and power production: A promising solution for a sustainable environment” [Sci. Total Environ. 825 (2022) 153892] - Meenal Gupta; Nishit Savla; Chetan Pandit; Soumya Pandit; Piyush Kumar Gupta; Manu Pant; Santimoy Khilari; Yogesh Kumar; Daksh Agarwal; Remya R. Nair; Dessy Thomas; Vijay Kumar Thakur (Science of The Total Environment, 2026)

Chlorine isotope compositions of the southern Tibetan lithosphere indicate a mantle source for chlorine in collisional porphyry Cu systems - Qiushi Zhou; Rui Wang; Chetan Nathwani; Heejin Jeon (Geochimica et Cosmochimica Acta, 2026)

Formulation, Optimization and Evaluation of Floating Microspheres of Glyburide and Metformin: A Novel Approach for Type 2 Diabetes Therapy - Deepak Khatkar; Anupama Setia; Mohit Chugh; Chetan Sabharwal; Diksha Jindal (Journal of Pharmaceutical Innovation, 2026)

Computational discovery of DENV-3 RdRp allosteric inhibitors: biological evaluation and mechanistic studies - Gokul Krishnan Nagendran; Swati Fageria; Divya Bhatt; Neetu Malya; Akansha Belwal; Shruti Gautam; Muskan Singhal; Ayesha Fatima; Mamta Choudhary; Vineeta Rai; Chetan D. Meshram; Sathish Kumar Mudedla (Molecular Diversity, 2026)

Effect of fabrication strategies on the uniformity, conductivity and reproducibility of nanomaterial modified conducting paper for the development of electrochemical biosensing devices - Chetan Ramesh Gawali; Ekta Daweshar; Pankaj; Utkarsha Sachin Kulkarni; Suveen Kumar (Next Research, 2026)

Ufasome-based transdermal dual-vesicular gel of febuxostat and aceclofenac for sustained gout therapy: formulation optimization and pharmacodynamic evaluation - Khyati Parekh; Vaishali Thakkar; Devesh Kapoor; Chetan Sojitra; Ankita Desai; Tejal Gandhi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Ulcer Protective Amoxicillin Trihydrate-loaded Alginate Beads Boosting Ulcer Treatment for Targeted H. Pylori Eradication - Chetan Deore; Santosh Butle; Shailesh Chalikwar; Jayesh Shivaji Patil (Journal of Pharmaceutical Innovation, 2026)

Automated Identification of Apple Leaf Diseases Under Field Conditions Using a High-Performance Deep Learning Framework - Chetan Sharma; Priya Sharma; Komal Sharma; Shamneesh Sharma; Hsin-Yuan Chen (Applied Fruit Science, 2026)

Diversification of structurally significant cycloartane-type triterpenes: exploiting beddomeilactone - Chetan Paul Singh; Aliya Tabassum; Ravindra S. Phatake; Yogesh P. Bharitkar (Natural Product Research, 2026)

Microbiome modulating remedies for chronic diseases: a review of current interventions and future directions - Mahendra Pratap Swain; Chetan Hasmukh Mehta; Bhrath Singh Padya; Shreya Sharma; Varalakshmi Velagacherla; Adwitiya Mitra; Satyajit Mohanty; Tuhin Mukherjee (Inflammopharmacology, 2026)

Ameliorative effects of Mucuna imbricata on inflammation and oxidative stress in a rat edema model - Suresh Suryawanshi; Chetan Aware; Viresh Thamke; Pratibha Mali; Balkrishna Shinde; Prakash Loni; Savita Tapase; Ranjit Gurav; Jyoti Jadhav (Inflammopharmacology, 2026)

Critical review of manganese sources, pollution, ecotoxicological risks, and mine remediation: Synthesis of a site-specific restoration framework - R.V. Akil Prasath; Chetan Dewangan; Tinku Kumar; Lal Singh (Journal of Environmental Management, 2026)

Explainable multimodal deep learning system for sustainable urban air quality forecasting and risk-aware recommendations - Basamma Umesh Patil; Chetan R; Harshitha V (Modeling Earth Systems and Environment, 2026)

Assessing Soil Contamination and Modeling Trace Element Uptake in Seed Spices of Rajasthan - Chetan Kumar Jangir; O. P. Aishwath; P. S. Sangwan; Dheeraj Panghaal; Harendra Kumar Yadav; Sanjay Kumar; S. N. Saxena; Vasundhara Sharma; Sandeep Kumar; Ram Swaroop Meena (International Journal of Environmental Research, 2026)

Assessment of pollinator visitation to ornamental plants associated with promoting biodiversity - Wonsoon Park; Sungsil Kim; Kyeongmin Mun; Byeongju An; Yuri Jang; Jongok Lim; Chetan Kaur; Yongsam Jeon; Geung-Joo Lee (Horticulture, Environment, and Biotechnology, 2026)

Breaking down barriers in Zika virus research: progressing immune pathogenesis research, international cooperation, and data sharing for preparedness - Vishavjeet Singh; Ahire Chetan Uddhav; Bikash Kumar Sah; Ankit Kumar (Journal of NeuroVirology, 2026)

Advanced vitrification and selective partitioning strategies for sustainable high-level radioactive liquid waste management - Jayaprakasam Selvakumar; Gattu Suneel; Chetan Parkash Kaushik (Chemosphere, 2026)

Building the blueprint: identifying key policy enablers for implementing PBSS in cities - Samir J. Patel; Chetan R. Patel; Gunjan Yadav (Innovative Infrastructure Solutions, 2026)

Unravelling the role of soil enzymatic activity as a vital bioindicator of soil health and fertility in agricultural systems - Ingudam Bhupenchandra; L. Devarishi Sharma; Menaka Devi Salam; Sumit Kumar; S.K. Chongtham; Anil K. Choudhary; H. Lembisana Devi; Soibam Sinyorita; Pranab Dutta; Ali Chenari Bouket; Tatiana Minkina; Chetan Keswani (Applied Soil Ecology, 2026)

A Global Meta-Analysis on Microbially-Assisted Phytoremediation of Heavy Metals in Contaminated Soils - Fedor D. Ivanov; Elizaveta P. Pulikova; Andrey V. Gorovtsov; Tatiana M. Minkina; Chetan Keswani (Water, Air, & Soil Pollution, 2026)

Discovery of novel purine analogues against breast cancer selectively targeting CDK2: optimization, synthesis, biological evaluation and docking study - Mahesh Rupapara; Nishith Teraiya; Chetan Sangani; Khushal Kapadiya; Nishant Patel (Molecular Diversity, 2026)

Albendazole-Para-Hydroxybenzoic Acid Cocrystals: A Lyophilization-Based Strategy for Enhanced Solubility and Therapeutic Performance - Jaydeep Mehta; Chetan Borkhataria; Payal Vaja; Saina Jyotishi (Journal of Pharmaceutical Innovation, 2026)

Polycystic ovary syndrome (PCOS): current insights, emerging therapeutics, and future treatment strategies - Mitali Panchpuri; Anglina Kisku; Ritu Painuli; Gaurav Pant; Chetan Kumar (Inflammopharmacology, 2026)

Ferroptosis-centered strategies: redefining therapeutic resistance & adaptation in modern oncology - Dineshkumar Madappan; Madhu Bommenahalli Krishnegowda; Prasiddhi Naik; Darshan Beejadi Raju; Lohith Hadapada; Yashwanth Sriramareddy; Chetan Patil; Prakash Goudanavar (Apoptosis, 2026)

Anti-parkinsonian effect of ethanolic extract of Anacyclus pyrethrum linn root in MPTP-induced neurodegeneration - Suresh Velayutham; Sri Indu Nataraj; Thamotharan Govindhaswamy; Muthukumaran Gurupackiyam; Anbarasi Balakrishnan; Chetan Ashok; Naveen Kumar Rajasekaran; Srikanth Jeyabalan (Next Research, 2026)

Electronic nose for agricultural grain pest detection, identification, and monitoring: A review - Chetan M. Badgujar; Sai Swaminathan; Alison R. Gerken (Journal of Stored Products Research, 2026)

Least ranked human individuals exhibit scale free behavioral responses in hierarchical social systems - Chetan K. Yadav (BioSystems, 2026)

Population genetic structure of commonly caught commercial shark species along the Indian coast - Sudha Kottillil; Chetan Rao; Kartik Shanker (Regional Studies in Marine Science, 2025)

Lithostructural controls of Pb-Cu-Ag mineralized veins of Jbel Addana district (Western Anti-Atlas, Morocco): Implications for mineral exploration - Zoubair El Ouad; Mohamed Alaeddine Belfoul; Mustapha Souhassou; Moha Ikenne; Chetan Nathwani; Mohamed Ez-zghoudy; Abdessamad El Atillah (Journal of African Earth Sciences, 2025)

Antidiabetic effect of spray dried camel milk powder formulations on the growth performance, histopathological and metagenomic investigation of high fat diet induced type-II diabetic Wistar rats - Subrota Hati; Krupali Ramanuj; Sreeja V; Kunal M. Gawai; Brijesh Bhuva; Kartikkumar Vadher; Prakash Koringa; Mansi Desai; Bhoomika Joshi; Tapan R. Kumbhani; Tejal Gandhi; Hital Shah; et al. (International Dairy Journal, 2025)

Woody species composition, biomass, and spatial diversity patterns in Bannerghatta National Park, Karnataka - Balasubramanya Sharma; P. Poorvashree; Narayan Kayet; A. K. Chakravarthy; H. C. Chetan; Noorunissa Begum; Debabrata Saha; H. S. Suresh (Tropical Ecology, 2025)

Unraveling the Seed Bio-priming Contours for Managing Plant Health - Sumit Kumar; R. Arutselvan; K. Greeshma; Shrey Bodhankar; A. U. Akash; Vurukonda Sai Shiva Krishna Prasad; Yasser Nehela; Udai B. Singh; Ingudam Bhupenchandra; Arnab Sen; Laxman Singh Rajput; Marina Burachevskaya; et al. (Journal of Plant Growth Regulation, 2025)

Development and Assessment of Tetrahydrocurcumin-Loaded Niosome-Based Thermosensitive In-situ Gel for the Treatment of Psoriasis - Akash Garg; Chetan Singh Chauhan; Rohitas Deshmukh (Journal of Pharmaceutical Innovation, 2025)

Clinical and molecular profile of 20 patients with DOCK8 deficiency—a single-center experience from Southern India - Neha Singh; Priya Ranganath; Ananthvikas Jayaram; Prerna Jhawar; Udhaya Kotecha; Jyothi Janardhanan; Harish Kumar; K. A Sudheer; Syed Mohammed Naushad Ali; Karthik Arigela; Chetan Ginigeri; Sagar Bhattad (Immunologic Research, 2025)

Structure-based virtual screening of β-tubulin and thioredoxin reductase in Brugia malayi: a step toward novel anti-filarial agents - Vrushali Patil; Ashish Asrondkar; Harshada Sawant; Chetan M. Jain; Dattatray Nandaram Thorat; Bhagwat Ramdas Patil (In Silico Pharmacology, 2025)

Long-Chained Fatty Acid-Based Solid Dispersions of Voriconazole as an Effective Strategy For Achieving Sustained Release - Urvi Modasiya; Kiran Dudhat; Sunny Shah; Chetan Borkhataria; Trupesh Pethani; Viral Shah; Chandankumar Pashavan; Gaurav Sanghvi; Akhil Hadiya; Mori Dhaval (AAPS PharmSciTech, 2025)

Comprehensive analysis of blackgram resistance to powdery mildew: Morphological, physiological and biochemical perspectives - V. Vasanthi; P. Kishore Varma; M. Suresh; N. Kamakshi; Ch Rani; D. Ramesh; K.K. Chetan; A. Bavana Keerthi; A. Janaki Prasad; B. Pushpa; J. Vasanthi (Physiological and Molecular Plant Pathology, 2025)

Comparative defense profiling in wheat near-isogenic lines reveals mechanistic diversity among stripe rust resistance (Yr) genes conferring uniform infection type against Puccinia striiformis f. sp. tritici - K.K. Chetan; Vaibhav Kumar Singh; O.P. Gangwar; Jayanth Kallugudi; Sanjeev Sharma; Bishnu Maya Bashyal; M.S. Saharan; M. Nishanth; M. Bharani (Physiological and Molecular Plant Pathology, 2025)

Drought risk and hydrological changes in the Ganga River Basin, India - Chetan Sharma; Deen Dayal; Anoop Kumar Shukla (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Discovery of three new cycloartane triterpene from Dysoxylum gotadhora - Chetan Paul Singh; Bhushan Rajendra Sonar; Nagaraju Nekkala; Yogesh P. Bharitkar (Natural Product Research, 2025)

Agricultural drought assessment using deep learning and multi-sensor remote sensing data integration - Prashant Kumar; Sonvane Chetan Chandrakant; Sudhanshu Ranjan; Akshar Tripathi (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Anatectic origin of the pegmatite-aplite dykes from the Paleoproterozoic basement of the Bas Draa inlier (Anti-Atlas-Morocco): Insights from whole rock geochemistry, Sm-Nd isotopes and tourmaline chemistry - Fatiha Askkour; Moha Ikenne; Brian L. Cousens; Mehdi Ousbih; Chetan Nathwani; Mustapha Souhassou; Mohamed Mahmoud Sebbab; Mohamed Ez-Zghoudy; Abdessamad El Atillah; Moulay Ahmed Boumehdi (Journal of African Earth Sciences, 2025)

Novel anticancer inhibitors targeting the PI3K/Akt/mTOR signaling route and apoptosis inducers: A study on the apoptosis mechanism via the intrinsic mitochondrial-mediated pathway - Digambar Yevale; Viralkumar Buha; Deepkumar U. Sangani; Nishith Teraiya; Chetan B. Sangani; Nishant Patel (Chemico-Biological Interactions, 2025)

Brain and behavior share features of a critical state dynamics - Chetan K. Yadav; Yoganarasimha Doreswamy (BioSystems, 2025)

A review on microbial-biofilm mediated mechanisms in marine microplastics degradation - Soumyajit Chandra; Dibyajit Lahiri; Moupriya Nag; Debasmita Bhattacharya; Chetan Pandit; Soumya Pandit; Kuldeep Sharma; Mithul Rajeev; Harjot Singh Gill; Sarvesh Rustagi (Antonie van Leeuwenhoek, 2025)

Amorphization of Albendazole Using Organic Acid-based Solid Dispersions for Improved Dissolution: A Solvent-free Approach - Nilesh Jambukiya; Kiran Dudhat; Sunny shah; Chetan Borkhataria; Trupesh Pethani; Ramesh Parmar; Viral Shah; Gaurav Sanghvi; Mori Dhaval (AAPS PharmSciTech, 2025)

Changing pattern of seed-associated fungi in urd bean (Vigna mungo (L.) Hepper): A study of diversity and abundance - A. Bavana Keerthi; P. Kishore Varma; S.L. Bhattiprolu; N. Kamakshi; A. Janaki Prasad; V. Vasanthi; B. Pushpa; K.K. Chetan (Physiological and Molecular Plant Pathology, 2025)

What is a circular economy champion? Defining a home-grown concept in an emerging field - Dolores Modic; Sahana Swaroop Chetan; Shajara Ul-Durar; Noman Arshed; Marco De Sisto; Nadja Damij (Journal of Cleaner Production, 2025)

Microalgal Bioethanol Production for Sustainable Development: Current Status and Future Prospects - Chetan Pandit; Soumya Pandit; Ramesh Chander Kuhad; Subhasree Ray; Santosh Kumar Mishra; Abhilasha Singh Mathuriya; Ram Prasad (Indian Journal of Microbiology, 2025)

Invasive woodlands and intruding dogs shape the structure of a mesocarnivore guild - Chetan Misher; Karani Singh Bithoo; Abi T. Vanak (Biological Invasions, 2025)

Unveiling the synergistic antimicrobial compatibility of fungal and bacterial bioagents against Sclerotium rolfsii in groundnut - V. Vasanthi; P. Kishore Varma; V. Chandrasekhar; Ch. Sreenivasa Rao; K. K. Chetan; G. Vamsi Krishna (Journal of Plant Pathology, 2025)

Strain-specific mutagenicity of NDMA and CPNP: insights from TA1535, TA100, and WP2 uvrA (pKM101) under metabolic activation - Chetan K. Kajavadara; Darshan T. Valani; Satyam N. Patel; Rushikesh M. Shukla; Laxit K. Bhatt; Rajesh J. Patel; Sunny P. Kumar; Rajesh Sundar; Mukul R. Jain (Environmental Toxicology and Pharmacology, 2025)

Nanocubospray of Epigallocatechin Gallate for Prevention of Oral Submucous Fibrosis - Chetan Hasmukh Mehta; Varalakshmi Velagacherla; Suman Manandhar; Yogendra Nayak; Karkala Sreedhara Ranganath Pai; Shruthi Acharya; Usha Yogendra Nayak (AAPS PharmSciTech, 2025)
NanoCubes loaded film-forming spray (NanoCuboSpray) is a new formulation that can be explored for nanoscale drug delivery. In the present work, epigallocatechin 3-gallate (EGCG) was encapsulated into NanoCuboSpray (NCS) for oral submucous fibrosis (OSF) treatment. The newly formulated EGCG NCS is then evaluated for ex vivo permeation, drug retention, in vivo efficacy, and safety. The developed formulation was homogeneous, viscous, spreadable and mucoadhesive on the buccal mucosa. EGCG NCS had good permeation and buccal mucosal retention in the ex vivo studies. The NCS with 81.81 mg/kg EGCG dose significantly enhanced mouth opening and effectively upregulated collagen and downregulated TGF-β1 in rats with areca nut extract-induced OSF. EGCG NCS demonstrated better improvements in histopathological and antioxidant parameters compared to EGCG hydrogel and betamethasone injection (BTM Inj.). In the safety evaluation, NCS treatment had negligible changes in histopathological features and serum biochemical markers, maintaining results comparable to the normal control group. Therefore, the optimized NCS presents a safer alternative strategy for treating OSF and holds the potential for further evaluation of its clinical efficacy. Graphical Abstract

Hot Melt Extruded Aceclofenac-Soluplus® Solid Dispersion: Mechanistic View of Miscibility and Drug-Carrier Interactions for Enhanced Dissolution - Likhitha U; Roushan Bharti; Reema Narayan; Chetan H. Mehta; Usha Yogendra Nayak (AAPS PharmSciTech, 2025)
Aceclofenac (ACF), a Non-Steroidal Anti-Inflammatory Drug (NSAID), is formulated with Soluplus® (SOLP) to enhance solubility and bioavailability. This study presents a distinct approach by utilizing Hot Melt Extrusion (HME) to prepare Aceclofenac-Soluplus® solid dispersion (ACF-SOLP), in contrast to the previously investigated nanoemulsion technique. The HME technique facilitates a uniform drug distribution within the polymer matrix, increasing ACF's dissolution rate. Different weight ratios of ACF and SOLP were assessed with 1:8 (HM4), which proved to be the optimal choice. ACF is dispersed within SOLP in its amorphous state, and HM4 exhibited a significant increase in drug release as compared to pure ACF and its physical mixture. I n vivo pharmacokinetic data of HM4 demonstrated a drastic improvement in the C max (7.1 ± 0.14 µg/ml) and AUC (12.1 ± 1.30 µg-h/ml). Further, molecular dynamics simulation revealed that the polymer is widely dispersed within the supramolecular architecture of ACF-SOLP, with ACF positioned centrally, confirming the favorable interactions between the components. Leveraging the hydrophilic nature of the SOLP, the solid dispersion demonstrated enhanced dissolution of ACF, while HME synergistically reinforced the combination. This approach presents a compelling alternative to traditional methods, unlocking new possibilities for formulating poorly soluble drugs. Graphical Abstract

Unveiling the Genetic Dynamics of Heat Stress Responses in Wheat RILs for Identifying Heat-Tolerant Genotypes - Mandeep Redhu; Vikram Singh; Somveer Nimbal; Ram Niwas; Atul Loyal; Chetan Singh; Mehdi Rahimi (Plant Molecular Biology Reporter, 2025)

Multifunctional Role of Brassinosteroids in Plant Growth, Development, and Defense - Nilanjan Chakraborty; Retwika Ganguly; Anik Sarkar; Disha Dasgupta; Jit Sarkar; Krishnendu Acharya; Marina Burachevskaya; Tatiana Minkina; Chetan Keswani (Journal of Plant Growth Regulation, 2025)

Bioengineering Bacillus spp. for Sustainable Crop Production: Recent Advances and Resources for Biotechnological Applications - Aurelio Ortiz; Estibaliz Sansinenea; Chetan Keswani; Tatiana Minkina; Satyendra Pratap Singh; Bhagwan Rekadwad; Rainer Borriss; Kathleen Hefferon; Trinh Xuan Hoat; Debasis Mitra; Pradeep Kumar Das Mohapatra; Periyasamy Panneerselvam (Journal of Plant Growth Regulation, 2025)
The goal of sustainable agriculture is to meet the rising need for food, while minimizing adverse impacts on the environment, protecting natural resources, and ensuring agricultural output over the long term. The pressing need to increase agricultural yield through sustainable agriculture is being emphasized. Several Bacillus species have been used as commercial biopesticides since they can act against plant pathogens by potentially suppressing them. At the same time, they can act as plant growth-promoting rhizobacteria and are known for their diverse characteristics and beneficial properties, making them potential candidates for use sustainable crop production programs. Knowledge of genetic information opens the door of possibility for understanding the way these microorganisms behave. By applying biotechnological tools to Bacillus , strategies can be adopted for the purpose of increasing the yield of crops and managing pests and pathogens that infect them. In this review, we identify the genes in the most significant Bacillus spp. that contribute to plant improvement. The most important biotechnological tools and advance computational approaches are described to provide an extended vision on this topic. However, increasing the crop production through application of beneficial microbial strains requires a multifaceted approach that considers ecological, economic, and social aspects. By implementing these strategies and practices, we can work towards a sustainable and resilient agricultural system that meets the growing food demand, while preserving the environment for future generations.

Harnessing microbial fuel cells for mitigating metal corrosion in offshore wind power infrastructure: Mechanisms, applications, and future prospects - Siddhant Srivastava; Chetan Pandit; Hsun-Yi Chen; Chin-Tsan Wang (Chemical Engineering Journal, 2025)

Deciphering the intra annual dynamics of evolving compound flood-drought interaction in Indian hydrology: insights from a copula-based approach - Salvadi Chetan Kumar; Velpuri Manikanta; Manoj Kumar Jain; Vivek Gupta (Theoretical and Applied Climatology, 2025)

Tailoring Drug Release Kinetics in Lipophilic Drug-Loaded Oral Microemulsions: Impact of Surfactant Chain Length - Himanshu Paliwal; Bhupendra G. Prajapati; Akshay Parihar; Mohammad Rashid Khan; Chetan Singh Chauhan (Journal of Pharmaceutical Innovation, 2025)

Insulin resistance in Alzheimer's disease: signalling mechanisms and therapeutics strategies - Mini Dahiya; Monu Yadav; Chetan Goyal; Anil Kumar (Inflammopharmacology, 2025)

Amorphous Solid Dispersion/Salt of Efavirenz: Investigating the Role of Molecular Interactions on Recrystallization and In-vitro Dissolution Performance - Aastha Gadoya; Kiran Dudhat; Sunny Shah; Chetan Borkhataria; Trupesh Pethani; Viral Shah; Nilesh Janbukiya; Saina Jyotishi; Jainabparvin Ansari; Mori Dhaval (AAPS PharmSciTech, 2025)

Ultrahigh and rapid removal of Ni2+ using a novel polymer-zeolite-biochar tri-composite through one-pot synthesis route - Sadamanti Sireesha; Madivada Sumanth; Chetan M. Patel; Inkollu Sreedhar (Environmental Research, 2025)

RNAi: A Potent Biotechnological Tool for Improvement of Ornamental Crops - Mukesh Kumar; Veena Chaudhary; Manoj Kumar Yadav; Chetan Chauhan; Ravi Kumar; Deepali Singh; Sachin Teotia (Plant Molecular Biology Reporter, 2025)

Nanocomposite Foils of PS/Cu : Dual Functionality of Optical Enhancement and Antibacterial Activity on Aeromonas hydrophila - Monika Barala; Jyoti Jaglan; Devendra Mohan; Namita Singh; Chetan Sharma; Sujata Sanghi (Indian Journal of Microbiology, 2025)

Mechanisms of microbe-assisted metal tolerance in phytoremediators: A review - Swati SACHDEV; Chetan KESWANI; Tatiana MINKINA; Kuldeep BAUDDH (Pedosphere, 2025)

Bicarbonate and nitrogen starvation: A dynamic duo for canthaxanthin accumulation in Chlorella saccharophila - Saeed uz Zafar; Anju Mehra; Chetan Paliwal; Pannaga Pavan Jutur (Journal of Applied Phycology, 2025)

Targeting InhA in drug-resistant Mycobacterium tuberculosis: potent antimycobacterial activity of diaryl ether dehydrozingerone derivatives - Mohamad Mosa Mubarak; Hadiya Amin Kantroo; Firdoous Ahmad Mir; Chetan Kumar; Zahoor Ahmad (Archives of Microbiology, 2025)

Pharmaceutical Salts: Comprehensive Insights From Fundamental Chemistry to FDA Approvals (2019–2023) - Mori Dhaval; Kiran Dudhat; Aastha Gadoya; Sunny shah; Trupesh Pethani; Nilesh Jambukiya; Ajay Patel; Chintan Kalsariya; Jainabparvin Ansari; Chetan Borkhataria (AAPS PharmSciTech, 2025)

Phosphoric acid–modified bentonite-chitosan composite beads: a novel and cost-effective adsorbent for multi-metal wastewater treatment - Khandgave Santosh Sopanrao; Akula Venugopal; Chetan Manharlal Patel; Inkollu Sreedhar (Environmental Science and Pollution Research, 2024)

Selection of solvent and positive control concentration for enhanced Ames test conditions for N-nitrosamine compounds - Chetan K. Kajavadara; Satyam N. Patel; Rushikesh M. Shukla; Darshan T. Valani; Rajesh J. Patel; Laxit K. Bhatt; Rajesh Sundar; Mukul R. Jain (Regulatory Toxicology and Pharmacology, 2024)

Technological advancements and sustainable practices in rock slope stability – Critical review - P. Rajendra Kumar; Kasinathan Muthukkumaran; Chetan Sharma (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Assessment of physio-biochemical assessment and gene expression analysis of sugarcane genotypes under water stress - Varsha Rani; R. S. Sengar; Chetan Chauhan (Molecular Biology Reports, 2024)

Temporal Impact of Elevated CO2 and Temperature on Solanum Lycopersicum L.: Insights into Growth, Phenology, Ultrastructure, Nutritional Quality and Metabolite Profile - Kavita Verma; Pooja Gokhale Sinha; Chetan; Vartika Mathur (Journal of Crop Health, 2024)

Unravelling Recent Advances in Ionizing Irradiation-Based Management of Post-Harvest Crop Losses: a Pan-Global Survey - Rusha Mitra; Paurabi Das; Krishnendu Acharya; Anindita Chakraborty; Ugo De Corato; Tatiana Minkina; Mikhail V. Kirichkov; Valery P. Kalinitchenko; Anik Sarkar; Chetan Keswani; Nilanjan Chakraborty (Journal of Crop Health, 2024)

Effect of dietary methionine levels on growth, carcass composition, physio-metabolic responses and haemato-biochemical parameters of juvenile Pacific white shrimp (Litopenaeus vannamei) reared in inland saline groundwater - Manas K. Maiti; Narottam P. Sahu; Parimal Sardar; Chetan K. Garg; Tincy Varghese; Naseemashahul Shamna; Ashutosh D. Deo (Animal Feed Science and Technology, 2024)

Efficacy of postharvest treatments with sodium nitroprusside and gibberellic acid on physio-biochemical modifications and vase life of dahlia cut flower - Chetan Chauhan; Mukesh Kumar; Varsha Rani; Rajat Singh (South African Journal of Botany, 2024)

Luminous Insights: Harnessing Carbon Nanodots from Black Seed Powder via Pyrolysis for Bioimaging and Antifungal Investigations - Urvi M. Lad; Nidhi P. Chunekar; Dhruti J. Dave; Bhumi N. Desai; Devesh H. Suthar; Chetan K. Modi (Journal of Fluorescence, 2024)

Optimization of dietary protein based on ideal protein concept for genetically improved farmed tilapia (GIFT) juveniles reared in inland saline water - Chetan K. Garg; Parimal Sardar; Narottam P. Sahu; Manas K. Maiti; Manish Jayant; Naseemashahul Shamna; Tincy Varghese; Ashutosh D. Deo; Vikas Kumar (Animal Feed Science and Technology, 2024)

Green Protocol for the Synthesis of Luminescent Carbon Nanodots Derived from Murraya Koenigii Leaves and Urea: Enhancing Photoluminescence for Advanced Bioimaging - Urvi M. Lad; Dhruti J. Dave; Bhumi N. Desai; Devesh H. Suthar; Chetan K. Modi (Journal of Fluorescence, 2024)

Transforming cantonments into net zero locality: a case study for replicating across India - Prashant P. Bhave; Chetan Dhawad; Vibha Jain (Environment, Development and Sustainability, 2024)

Plant, bacteria and fungi crosstalk: Direct and indirect biocontrol mechanisms of sugarcane rhizoplane Pseudomonas species against Fusarium wilt - K.K. Chetan; P. Kishore Varma; V. Chandrasekhar; P. Anil Kumar; V. Vasanthi (Rhizosphere, 2024)

Microplastics and heavy metal contamination along a land-use gradient in a Himalayan foothill river: Prevalence and controlling factors - Sunil Kumar; Diptimayee Behera; Kumar Ajay; Balasubramanian Karthick; Chetan Dharia; Ambili Anoop (Journal of Contaminant Hydrology, 2024)

Rural-urban transition and food security in India - Chetan Choithani; Abdul Jaleel CP; S Irudaya Rajan (Global Food Security, 2024)

Exploring the performance of biocatalysts for biohydrogen production - Chetan Pandit; Mohit Kumar; Ramesh Chander Kuhad; Kuldeep Sharma; Amit Roy; Rishikesh Shukla; Soumya Pandit; Nishant Ranjan; Santosh Kumar Mishra; Ram Prasad (Biocatalysis and Agricultural Biotechnology, 2024)

Assessment of spatial variability of precipitation in Krishna River Basin using a metric based on apportionment entropy - Salvadi Chetan Kumar; Siva Sai Syam N; Maheswaran Rathinasamy (Hydrological Sciences Journal, 2024)

Agricultural object detection with You Only Look Once (YOLO) Algorithm: A bibliometric and systematic literature review - Chetan M Badgujar; Alwin Poulose; Hao Gan (Computers and Electronics in Agriculture, 2024)

Analysis of household car and two-wheeler ownership considering spatial dependency - Chetan Doddamani; Piyali Majumder; M. Manoj (Transportation Research Part D: Transport and Environment, 2024)

Scoparone chemical modification into semi-synthetic analogues featuring 3-substitution for their anti-inflammatory activity - Chetan Kumar; Pankaj Chibber; Ritu Painuli; Syed Assim Haq; Ram A. Vishwakarma; Gurdarshan Singh; Naresh K. Satti; Ravindra S. Phatake (Molecular Diversity, 2024)

Two new cycloartane type triterpenes from Dysoxyllum binectariferum - Chetan Paul Singh; Akshima Sharma; Kajal Sharma; Priya Darshani; Anil Katare; Deepak Kumar; Yogesh P. Bharitkar (Natural Product Research, 2024)

Organic matter sources and distribution along land-use gradient in a Himalayan foothills River: Insights from molecular markers - Diptimayee Behera; Dharia Chetan; Ambili Anoop (Environmental Research, 2024)

Analysis of effect of weather variables on diseases of winter season fodder crops - Ashlesha Atri; Chetan Singla; Rohit Sharma (Theoretical and Applied Climatology, 2024)

Sustained inactivation of the Polycomb PRC1 complex induces DNA repair defects and genomic instability in epigenetic tumors - Chetan C. Rawal; Vincent Loubiere; Nadejda L. Butova; Juliette Gracia; Victoria Parreno; Chiara Merigliano; Anne-Marie Martinez; Giacomo Cavalli; Irene Chiolo (Histochemistry and Cell Biology, 2024)
Cancer initiation and progression are typically associated with the accumulation of driver mutations and genomic instability. However, recent studies demonstrated that cancer can also be driven purely by epigenetic alterations, without driver mutations. Specifically, a 24-h transient downregulation of polyhomeotic ( ph -KD), a core component of the Polycomb complex PRC1, is sufficient to induce epigenetically initiated cancers (EICs) in Drosophila , which are proficient in DNA repair and characterized by a stable genome. Whether genomic instability eventually occurs when PRC1 downregulation is performed for extended periods of time remains unclear. Here, we show that prolonged depletion of PH, which mimics cancer initiating events, results in broad dysregulation of DNA replication and repair genes, along with the accumulation of DNA breaks, defective repair, and widespread genomic instability in the cancer tissue. A broad misregulation of H2AK118 ubiquitylation and to a lesser extent of H3K27 trimethylation also occurs and might contribute to these phenotypes. Together, this study supports a model where DNA repair and replication defects accumulate during the tumorigenic transformation epigenetically induced by PRC1 loss, resulting in genomic instability and cancer progression.

L-Arginine Doped Carbon Nanodots from Cinnamon Bark for Improved Fluorescent Yeast Cell Imaging - Urvi M. Lad; Dhruti J. Dave; Bhumi N. Desai; Devesh H. Suthar; Chetan K. Modi (Journal of Fluorescence, 2024)

Identification of potential Akt activators: a ligand and structure-based computational approach - Harish B. Kumar; Suman Manandhar; Ekta Rathi; Shama Prasada Kabekkodu; Chetan Hasmukh Mehta; Usha Yogendra Nayak; Suvarna G. Kini; K. Sreedhara Ranganath Pai (Molecular Diversity, 2024)
The Akt pathway plays a significant role in various diseases like Alzheimer’s, Parkinson’s, and Diabetes. Akt is the central protein whose phosphorylation controls many downstream pathways. Binding of small molecules to the PH domain of Akt facilitates its phosphorylation in the cytoplasm and upregulates the Akt pathway. In the current study, to identify Akt activators, ligand-based approaches like 2D QSAR, shape, and pharmacophore-based screening were used, followed by structure-based approaches such as docking, MM-GBSA, ADME prediction, and MD simulation. The top twenty-five molecules from the Asinex gold platinum database found to be active in most 2D QSAR models were used for shape and pharmacophore-based screening. Later docking was performed using the PH domain of Akt1 (PDB: 1UNQ), and 197105, 261126, 253878, 256085, and 123435 were selected based on docking score and interaction with key residues, which were druggable and formed a stable protein–ligand complex. MD simulations of 261126 and 123435 showed better stability and interactions with key residues. To further investigate the SAR of 261126 and 123435, derivatives were downloaded from PubChem, and structure-based approaches were employed. MD simulation of derivatives 12289533, 12785801, 83824832, 102479045, and 6972939 was performed, in which 83824832 and 12289533 showed interaction with key residues for a longer duration of time, proving that they may act as Akt activators.

Unveiling the Biocontrol Potential of Rhizoplane Bacillus Species against Sugarcane Fusarium Wilt through Biochemical and Molecular Analysis - K. K. Chetan; P. Kishore Varma; V. Chandrasekhar; P. Anil Kumar; V. Vasanthi; G. Vamshi Krishna (Brazilian Journal of Microbiology, 2024)

Challenges and strategies for waste food anaerobic digestion: insights and future directions - Asma Musfira Shabbirahmed; Prathap Somu; Hsi-Hsien Yang; Samson Prince Hiruthyaswamy; Chetan Shekhar Karua; Akhilesh Kumar Yadav (Environment, Development and Sustainability, 2024)

Wired for energy: Electromethanogenesis redefining anaerobic digestion - Soumya Pandit; Chetan Pandit; Abhilasha Singh Mathuriya; Soumya Chatterjee; Dipak A. Jadhav; Krishna Kumar Yadav; Mohammad Khalid (Process Safety and Environmental Protection, 2024)

Agricultural policies for mitigating groundwater depletion in central Punjab - Chetan Singla; Rajan Aggarwal; Samanpreet Kaur (Groundwater for Sustainable Development, 2024)

Nurturing health through millet derived nutraceuticals - Rashmi Rani; Chetan Pandey; Neha Kapoor (Food and Humanity, 2024)

Multifaceted roles of plant glycosyl hydrolases during pathogen infections: more to discover - Muthusaravanan Sivaramakrishnan; Chetan Veeraganti Naveen Prakash; Balakumaran Chandrasekar (Planta, 2024)

The efficient applications of native flora for phytorestoration of mine tailings: a pan-global survey - Ankit Abhilash Swain; Pallavi Sharma; Chetan Keswani; Tatiana Minkina; Purushotham Tukkaraja; Venkataramana Gadhamshetty; Sanjeev Kumar; Kuldeep Bauddh; Narendra Kumar; Sushil Kumar Shukla; Manoj Kumar; Rama Shanker Dubey; et al. (Environmental Science and Pollution Research, 2024)

A concise review on biorefinery remedies for biomethanol production and processing - Mayur Thakare; Soumya Pandit; Chetan Pandit; Subhasree Ray; Abdullah M. Alkahtani; Khulood Fahad Alabbosh; Nishant Ranjan; S.J. Geetha; Sanket J. Joshi (Biocatalysis and Agricultural Biotechnology, 2024)

Brassinolide enhances glucosinolates biosynthesis in shoot culture of Chinese cabbage (Brassica rapa ssp. pekinensis) - Ganeshan Sivanandhan; Jiae Moon; Chaemin Sung; Solhee Bae; Chetan Kaur; Natesan Selvaraj; Yong Pyo Lim (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Development of Epigallocatechin 3-gallate-Loaded Hydrogel Nanocomposites for Oral Submucous Fibrosis - Chetan Hasmukh Mehta; Varalakshmi Velagacherla; Suman Manandhar; Yogendra Nayak; Sreedhara Ranganath K Pai; Shruthi Acharya; Usha Yogendra Nayak (AAPS PharmSciTech, 2024)
Oral submucous fibrosis (OSF) is a chronic progressive disease associated with increased collagen deposition and TGF-β1 release. The current therapy and management have been a limited success due to low efficacy and adverse drug reactions. This study aimed to evaluate epigallocatechin 3-gallate (EGCG) encapsulated nanoparticles loaded mucoadhesive hydrogel nanocomposite (HNC) for OSF. Developed HNC formulations were evaluated for their permeation behaviour using in vitro as well as ex vivo studies, followed by evaluation of efficacy and safety by in vivo studies using areca nut extract-induced OSF in rats. The disease condition in OSF-induced rats was assessed by mouth-opening and biochemical markers. The optimized polymeric nanoparticles exhibited the required particle size (162.93 ± 13.81 nm), positive zeta potential (22.50 ± 2.94 mV) with better mucoadhesive strength (0.40 ± 0.002 N), and faster permeation due to interactions of the positively charged surface with the negatively charged buccal mucosal membrane. HNC significantly improved disease conditions by reducing TGF-β1 and collagen concentration without showing toxicity and reverting the fibroid buccal mucosa to normal. Hence, the optimized formulation can be further tested to develop a clinically alternate therapeutic strategy for OSF. Graphical Abstract

Effect of various chemical solutions on micropropagation efficiency, antioxidant activities and clonal fidelity analysis of in vitro developed plantlets in pomegranate (Punica granatum L.) using SSR markers - Devendra Pal; Mukesh Kumar; Manoj Kumar Yadav; Chetan Chauhan; Arvind Kumar; Ujjwal Sirohi; V. Rakesh Sharma; Veena Chaudhary (Vegetos, 2024)

Strategies for mitigation of pesticides from the environment through alternative approaches: A review of recent developments and future prospects - Veena Chaudhary; Mukesh Kumar; Chetan Chauhan; Ujjwal Sirohi; Arun Lal Srivastav; Lata Rani (Journal of Environmental Management, 2024)

Long-term hygrothermal performance assessment of wood-frame walls considering climate uncertainties using partial least squares (PLS) regression - Chetan Aggarwal; Lin Wang; Hua Ge; Maurice Defo; Michael Lacasse (Energy and Buildings, 2024)

HIF-PHD inhibitor desidustat ameliorates iron deficiency anemia - Vishal J. Patel; Amit Joharapurkar; Samadhan G. Kshirsagar; Maulik S. Patel; Hardikkumar H. Savsani; Harshad S. Dodiya; Milan H. Rakhasiya; Chetan Kajavadara; Darshan Valani; Mukul R. Jain (Toxicology and Applied Pharmacology, 2024)

Novel soy protein isolate/sodium alginate-based functional aerogel for efficient uptake of organic dye from effluents - Chetan C. Revadekar; Chirag Batukbhai Godiya; Bum Jun Park (Journal of Environmental Management, 2024)

Degradation of food dyes via biological methods: A state-of-the-art review - Vandana Singh; Chetan Pandit; Arpita Roy; Soumya Pandit; Ashutosh Kumar Rai; Anju Rani; Nishant Ranjan; Sarvesh Rustagi; Sumira Malik (Bioresource Technology Reports, 2024)

Impact of the sustainable agricultural practices for governing soil health from the perspective of a rising agri-based circular bioeconomy - Ugo De Corato; Egidio Viola; Chetan Keswani; Tatiana Minkina (Applied Soil Ecology, 2024)

Genomic profiling and characteristics of a C1 degrading heterotrophic fresh-water bacterium Paracoccus sp. strain DMF - Shiwangi Maurya; Chetan Kumar Arya; Nidhi Parmar; Nitish Sathyanarayanan; Chaitanya G. Joshi; Gurunath Ramanathan (Archives of Microbiology, 2024)

Real-time stored product insect detection and identification using deep learning: System integration and extensibility to mobile platforms - Chetan M. Badgujar; Paul R. Armstrong; Alison R. Gerken; Lester O. Pordesimo; James F. Campbell (Journal of Stored Products Research, 2023)

Study on the Correlation Between Nimodipine (BCS Class II) Solubility, Dissolution Improvement, and Brain Tissue Concentration Through Cocrystallization - Nilam Rathod; Chetan Borkhataria; Ravi Manek; Vidhi Patel; Nilesh Patel; Kalpesh Patel; Jalpa Paun; Dhruv Sakhiya (Journal of Pharmaceutical Innovation, 2023)

Para-Hydroxy Benzoic Acid Coformer Enable Enhanced Solubility, Dissolution, and Antifungal Activity of Ketoconazole Cocrystals - Jaydeep Mehta; Chetan Borkhataria; Ajay Patel; Ravi Manek; Nilesh Patel; Dhruv Sakhiya; Krupal Shanishchara; Bhargvi Mistry (Journal of Pharmaceutical Innovation, 2023)

Insight into the metabolic pathways of Paracoccus sp. strain DMF: a non-marine halotolerant methylotroph capable of degrading aliphatic amines/amides - Chetan Kumar Arya; Shiwangi Maurya; Gurunath Ramanathan (Environmental Science and Pollution Research, 2023)

Studies on genetic variability based on different morpho-physiological traits vis-à-vis diversity assessment of China aster [Callistephus chinensis (L.) Nees] genotypes - Chetan Mugali; Indrajit Sarkar; Manoj Kanti Debnath; Puspendu Dutta; Rajiv Kumar (Vegetos, 2023)

Identification of phytochemical as a dual inhibitor of PI3K and mTOR: a structure-based computational approach - B. Harish Kumar; Suman Manandhar; Sneha Sunil Choudhary; Keerthi Priya; Tanvi V. Gujaran; Chetan Hasmukh Mehta; Usha Yogendra Nayak; K. Sreedhara Ranganath Pai (Molecular Diversity, 2023)
Breast cancer is a common form of cancer that affects both men and women. One of the most common types of genomic flaws in cancer is the aberrations in the PI3K/AKT/mTOR pathway. The benefit of dual targeting PI3K as well as mTOR is that the kinase-positive feedback loops are more effectively inhibited. Therefore, in the current study, structure-based models like molecular docking, MM-GBSA, Qikprop, induced fit docking, simulated molecular dynamics (MD), and thermal MM-GBSA were used to identify the phytochemicals from the zinc 15 database, which may inhibit PI3K and mTOR. After docking the phytochemicals with PI3K (PDB 4FA6), ten ligands based on the docking score were selected, among which salvianolic acid C had the highest docking score. Hence, salvianolic acid A was also docked. All the ligands taken showed a binding energy of greater than − 30 kcal/mol. The predicted ADME showed that the ligands have druggable properties. By performing MD of the top five ligands and salvianolic acid A, it was found that ZINC000059728582, ZINC000257545754, ZINC000253532301, and salvianolic acid A form a stable complex with PI3K protein, among which ZINC000014690026 showed interaction with Val 882 for more than 89% of the time. Salvianolic acid A is already proven to suppress tumor growth in acute myeloid leukemia by inhibiting PI3K/AKT pathway, but the exact protein target is unknown. Therefore, the present study identifies new molecules and provides evidence for salvianolic acid A for dual inhibition. Further experiments must be performed both in vitro and in vivo to support the predictions of these computational tools. Graphical abstract

Unraveling the Plant Growth-Promoting Mechanisms of Stenotrophomonas sp. CV83 for Drought Stress Tolerance and Growth Enhancement in Chickpea - Anjney Sharma; Anukool Vaishnav; Hena Jamali; Chetan Keswani; Alok Kumar Srivastava; Rajeev Kaushik; Saurabh Gupta; Y. K. Bansal (Journal of Plant Growth Regulation, 2023)

Polyphenol-based targeted therapy for oral submucous fibrosis - Chetan Hasmukh Mehta; Shivangi Paliwal; Manjunatha S. Muttigi; Raviraja N. Seetharam; Alevoor Srinivas Bharath Prasad; Yogendra Nayak; Shruthi Acharya; Usha Yogendra Nayak (Inflammopharmacology, 2023)
Oral submucous fibrosis (OSF) is a chronic, progressive, and precancerous condition mainly caused by chewing areca nut. Currently, OSF therapy includes intralesional injection of corticosteroids with limited therapeutic success in disease management. Therefore, a combined approach of in silico , in vitro and in vivo drug development can be helpful. Polyphenols are relatively safer than other synthetic counterparts. We used selected polyphenols to shortlist the most suitable compound by in silico tools. Based on the in silico results, epigallocatechin-3-gallate (EGCG), quercetin (QUR), resveratrol, and curcumin had higher affinity and stability with the selected protein targets, transforming growth factor beta-1 (TGF-β1), and lysyl oxidase (LOX). The efficacy of selected polyphenols was studied in primary buccal mucosal fibroblasts followed by in vivo areca nut extract induced rat OSF model. In in vitro studies, the induced fibroblast cells were treated with EGCG and QUR. EGCG was safer at higher concentrations and more efficient in reducing TGF-β1, collagen type-1A2 and type-3A1 mRNA expression than QUR. In vivo studies confirmed that the EGCG hydrogel was efficient in improving the disease conditions compared to the standard treatment betamethasone injection with significant reduction in TGF-β1 and collagen concentrations with increase in mouth opening. EGCG can be considered as a potential, safer and efficient phytomolecule for OSF therapy and its mucoadhesive topical formulation help in the improvement of patient compliance without any side effects. Graphical abstract Highlights Potential polyphenols were shortlisted to treat oral submucous fibrosis (OSF) using in silico tools Epigallocatechin 3-gallate (EGCG) significantly reduced TGF-β1 and collagen both in vitro and in vivo EGCG hydrogel enhanced antioxidant defense, modulated inflammation by reducing TGF-β1 and improved mouth opening in OSF rat model.

Identifying common stored product insects using automated deep learning methods - Chetan M. Badgujar; Paul R. Armstrong; Alison R. Gerken; Lester O. Pordesimo; James F. Campbell (Journal of Stored Products Research, 2023)

Nano-Inputs: A Next-Generation Solution for Sustainable Crop Production - Satyendra Pratap Singh; Chetan Keswani; Tatiana Minkina; Aurelio Ortiz; Estibaliz Sansinenea (Journal of Plant Growth Regulation, 2023)

Elimination of senescent cells by treatment with Navitoclax/ABT263 reverses whole brain irradiation-induced blood-brain barrier disruption in the mouse brain - Rafal Gulej; Ádám Nyúl-Tóth; Chetan Ahire; Jordan DelFavero; Priya Balasubramanian; Tamas Kiss; Stefano Tarantini; Zoltan Benyo; Pal Pacher; Boglarka Csik; Andriy Yabluchanskiy; Peter Mukli; et al. (GeroScience, 2023)

In Silico Screening as a Tool to Prepare Drug-Drug Cocrystals of Ibrutinib-Ketoconazole: a Strategy to Enhance Their Solubility Profiles and Oral Bioavailability - Divya Dhatri Kara; Pragathi Devanand Bangera; Chetan Hasmukh Mehta; Katikala Tanvi; Mahalaxmi Rathnanand (AAPS PharmSciTech, 2023)
Ibrutinib (IBR) is a biopharmaceutical classification system (BCS) class II drug and an irreversible Bruton’s tyrosine kinase (BTK) inhibitor. IBR has an extremely low oral bioavailability due to the activity of the CYP3A4 enzyme. The current intention of the research was to enhance solubility followed by oral bioavailability of IBR using the hot melt extrusion (HME) technique by formulating drug-drug cocrystals (DDCs). Ketoconazole (KET) is an active CYP3A4 inhibitor and was selected based on computational studies and solubility parameter prediction. Differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), powder X-ray diffraction (PXRD), thermogravimetric analysis (TGA), proton nuclear magnetic resonance ( 1 H NMR), and scanning electron microscopy (SEM) evaluations were employed for estimating the formation of IBR-KET DDCs. The IBR-KET DDC system was discovered to have a hydrogen bond (H-bond) and π-π-stacking interactions, in accordance with the computational results. Further, IBR-KET DDCs showed enhanced solubility, stability, powder dissolution, in vitro release, and flow properties. Furthermore, IBR-KET-DDCs were associated with enhanced cytotoxic activity in K562-CCL-243 cancer cell lines when compared with IBR and KET alone. In vivo pharmacokinetic studies have shown an enhanced oral bioavailability of up to 4.30 folds of IBR and 2.31 folds of KET through IBR-KET-DDCs compared to that of the IBR and KET suspension alone. Thus, the prepared IBR-KET-DDCs using the HME technique stand as a favorable drug delivery system that augments the solubility and oral bioavailability of IBR along with KET. Graphical abstract

Dereplication approach for the first time isolation of tatarinowin a and pentadecanoic acid from Acorus calamus L. by using GC-MS - Chetan Kumar; Sabiyah Akhter; Naresh Kumar Satti; Vivek Kumar Gupta; Siya Ram Meena; Ram Vishwakarma; Qazi Parvaiz Hassan; Mahendra Kumar Verma (Natural Product Research, 2023)

Synthesis of oxadiazole-thiadiazole fluorochromane hybrids and their antioxidant activity - Mahesh Rupapara; Mehul Chauhan; Chetan B. Sangani; Mohd Afzal; Abdullah Alarifi; Maria Christy; Khushal Kapadiya (Journal of Fluorine Chemistry, 2023)

An environmentally benign oil dispersion/phytoextract system for improved retention upon foliage and control of aphids in spice crops - Smriti Kala; Amrish Agarwal; Krishna Kant; B.K. Mishra; Nisha Sogan; Natish Kumar; Chetan K.D. Jawle; Dipak Kumar Hazara; Jitendra Kumar (Journal of Cleaner Production, 2023)

Leveraging GIS to deploy demand-driven public charging infrastructure in an Indian Metropolitan city - Apurvkumar Desai; Chetan R. Patel (Spatial Information Research, 2023)

The Impacts of Urban Growth Drivers on the Spatial and Temporal Pattern of City Expansion - Kaushikkumar P. Sheladiya; Chetan R. Patel (Journal of the Indian Society of Remote Sensing, 2023)

Apatite evidence for a fluid-saturated, crystal-rich magma reservoir forming the Quellaveco porphyry copper deposit (Southern Peru) - Chetan L. Nathwani; Simon J. E. Large; Emily R. Brugge; Jamie J. Wilkinson; Yannick Buret (Contributions to Mineralogy and Petrology, 2023)
Large volume, intermediate-felsic magma reservoirs are the source of melt and mineralising fluids which generate porphyry copper deposits. Cooling and crystallisation of hydrous magmas drives the exsolution and expulsion of a magmatic volatile phase—a process which remains challenging to constrain in porphyry Cu systems where the record of magma volatile compositions is rarely preserved. Here, we use the halogen compositions of apatite inclusions shielded as inclusions within zircon to constrain volatile evolution in magma reservoirs which pre-date and are synchronous with porphyry Cu mineralisation at Quellaveco, Southern Peru. Geochemical and textural data confirm that the zircon-included apatites escaped re-equilibration with hydrothermal fluids, unlike apatites found in the groundmass of the same rocks. We, therefore, recommend that future studies attempting to reconcile magmatic volatile budgets using apatite in porphyry Cu systems should focus on apatite inclusions in zircon. By combining the apatite inclusion data with numerical modelling, we find evidence that the magma reservoir sourcing porphyry Cu mineralisation remained fluid-saturated for the entire period recorded by apatite crystallisation. By contrast, the pre-mineralisation batholith shows more variable, potentially fluid-undersaturated behaviour. Our modelling suggests that in order to attain the porphyry melt volatile compositions inferred from apatite, the magma reservoir must have exsolved a large proportion of its volatile budget, consistent with having been held at high crystallinity (40–60% crystals). This crystallisation interval coincides with peak chlorine and copper extraction from intermediate-felsic magmas, and would have permitted efficient fluid migration and accumulation at the roof of the system. We suggest that the storage of large-volume, long-lived, crystal-rich magma reservoirs in magmatic arcs may be a critical step in generating world-class porphyry copper deposits.

Insights from catch composition and historical records of elasmobranchs in the Malvan fishery on the central west coast of India - Shruthi Kottillil; Trisha Gupta; Muralidharan Manoharakrishnan; Chetan Rao; Kartik Shanker (Journal of Fish Biology, 2023)
Although elasmobranchs (sharks and rays) are highly threatened by fisheries, there are few studies that examine gear and fishery effects on catch composition and abundance across India, one of the top elasmobranch fishing nations globally. We assessed elasmobranch diversity, abundance, catch rates and fishery characteristics using landing surveys in Malvan on the central‐western coast of India, a major multi‐gear, multi‐species fishing centre, over three sampling periods from February 2018 to March 2020. We sampled 3145 fishing trips and recorded 27 elasmobranch species, of which nearly half are categorised as “Threatened” by the IUCN. In addition, we documented historical records by compiling information from identification guides, research papers, articles and reports. During the study period, the catch was dominated by small‐sized coastal species like the spadenose shark ( Scoliodon laticaudus ) and the scaly whipray ( Brevitrygon walga ). Trawlers accounted for 64.9% of the catch, highest by number, and captured smaller‐sized individuals. Nonetheless, artisanal and gillnet fisheries had higher catch per unit effort (CPUE) for rays (5.1 ± 1.0) and sharks (10 ± 1.0), respectively, and captured significantly larger‐sized individuals. Through generalised linear models, we found seasonal, gear and fishery effects on the abundance and size of commonly caught species. The presence of neonates and gravid females of multiple species also suggests nursery grounds in this region. Historically, 141 species have been recorded in this region, and a comparison with current catch suggests a shift in elasmobranch community structure and potential mesopredator release. This study emphasises the importance of gear and species‐specific research for conservation planning at the local level and suggests the need for management strategies with fisher cooperation.

Aluminum Toxicity in Plants: Present and Future - Roghieh Hajiboland; Chetan K. Panda; Oksana Lastochkina; Marina A. Gavassi; Gustavo Habermann; Jorge F. Pereira (Journal of Plant Growth Regulation, 2023)

Assessing mould growth risk of wood-frame walls using partial least squares (PLS) regression considering climate model uncertainties - Chetan Aggarwal; Hua Ge; Maurice Defo (Building and Environment, 2023)

Ultrasound-promoted convenient and ionic liquid [BMIM]BF4 assisted green synthesis of diversely functionalized pyrazolo quinoline core via one-pot multicomponent reaction, DFT study and pharmacological evaluation - Dipakkumar D. Chudasama; Manan S. Patel; Jaydeepkumar N. Parekh; Harsh C. Patel; Chetan V. Rajput; Navin P. Chikhaliya; Kesur R. Ram (Molecular Diversity, 2023)

Correlation of leaf trichome density and stomatal parameters of some commercial sugarcane genotypes to orange rust incidence and severity - P. Kishore Varma; V. Chandrasekhar; M. Charumati; M. Bharathalakshmi; R. Manjula; G. Vamsi Krishna; K. K. Chetan; V. Vasanthi (Indian Phytopathology, 2023)

Life cycle assessment of revalorization of lignocellulose for the development of biorefineries - Srijoni Banerjee; Chetan Pandit; Marttin Paulraj Gundupalli; Soumya Pandit; Nishant Rai; Dibyajit Lahiri; Kundan Kumar Chaubey; Sanket J. Joshi (Environment, Development and Sustainability, 2023)

Extraction optimization of anti-Parkinson’s medication L-DOPA and bioactive compounds from Mucuna atropurpurea (Roxb.) Wight & Arn. with biomedical potential: RSM based desirability function approach - Pratibha Mali; Prajakta Kamble; Chetan Aware; Suresh Suryawanshi; Jyoti Jadhav (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Effect of graded levels of dietary methionine on growth performance, carcass composition and physio-metabolic responses of genetically improved farmed tilapia (GIFT) juveniles reared in inland saline water of 10 ppt - Chetan K. Garg; Parimal Sardar; Narottam P. Sahu; Manas K. Maiti; Naseemashahul Shamna; Tincy Varghese; Ashutosh D. Deo (Animal Feed Science and Technology, 2023)

Trichoderma viride—Mediated Modulation of Oxidative Stress Network in Potato Challenged with Alternaria solani - Sumit Kumar; Ram Chandra; Chetan Keswani; Tatiana Minkina; Saglara Mandzhieva; Marina Voloshina; Mukesh Meena (Journal of Plant Growth Regulation, 2023)

Microalgal pandora for potent bioenergy production: A way forward? - Srijoni Banerjee; Dipankar Ghosh; Chetan Pandit; Sagnik Saha; Anwesha Mohapatra; Soumya Pandit; Minaxi Sharma; Kandi Sridhar; Baskaran Stephen Inbaraj; Ram Prasad (Fuel, 2023)

Metabarcoding reveals high genetic diversity of harmful algae in the coastal waters of Texas, Gulf of Mexico - Chetan C. Gaonkar; Lisa Campbell (Harmful Algae, 2023)

Narrowing fossil fuel consumption in the Indian road transport sector towards reaching carbon neutrality - M.S. Hossain; Yan Ru Fang; Teng Ma; Chen Huang; Wei Peng; Johannes Urpelainen; Chetan Hebbale; Hancheng Dai (Energy Policy, 2023)

Illuminating the signalomics of microbial biofilm on plant surfaces - Sanchita Bipin Patwardhan; Chetan Pandit; Soumya Pandit; Devvret Verma; Dibyajit Lahiri; Monupriya Nag; Rina Rani Ray; Priyanka Jha; Ram Prasad (Biocatalysis and Agricultural Biotechnology, 2023)

Recent trends of green human resource management: Text mining and network analysis - Chetan Sharma; Sumit Sakhuja; Shivinder Nijjer (Environmental Science and Pollution Research, 2022)

Effects of differently incubated cupric oxide nanoparticles on the granulosa cells of caprine ovary in vitro - Chetan Kumar; Rajnesh Kumar Sharma (Environmental Science and Pollution Research, 2022)

Nitrogen stress-induced TaDof1 expression in diverse wheat genotypes and its relation with nitrogen use efficiency - Alka Bharati; Gayatri Tehlan; Chetan Kumar Nagar; Subodh Kumar Sinha; Karnam Venkatesh; Pranab Kumar Mandal (Cereal Research Communications, 2022)

De novo transcriptome analysis for exploration of genes responding to salinity in a halophyte New Zealand spinach (Tetragonia tetragonioides) - Chetan Kaur; Bashistha Kumar Kanth; Ka Youn Lee; Shipra Kumari; Geung-Joo Lee (Plant Biotechnology Reports, 2022)

Drug-Carrier Miscibility in Solid Dispersions of Glibenclamide and a Novel Approach to Enhance Its Solubility Using an Effervescent Agent - Muralidhar Pisay; K. Vijaya Bhaskar; Chetan Hasmukh Mehta; Usha Yogendra Nayak; Kunnatur Balasundara Koteshwara; Srinivas Mutalik (AAPS PharmSciTech, 2022)
The present research aims to investigate the miscibility, physical stability, solubility, and dissolution rate of a poorly water-soluble glibenclamide (GLB) in solid dispersions (SDs) with hydrophilic carriers like PEG-1500 and PEG-50 hydrogenated palm glycerides (Acconon). Mathematical theories such as Hansen solubility parameters, Flory Huggins theory, Gibbs free energy, and the in silico molecular dynamics simulation study approaches were used to predict the drug-carrier miscibility. To increase the solubility further, the effervescence technique was introduced to the conventional solid dispersions to prepare effervescent solid dispersions (ESD). Solid dispersions (SDs) were prepared by microwave, solvent evaporation, lyophilization, and hot melt extrusion (HME) techniques and tested for different characterization parameters. The theoretical and in silico parameters suggested that GLB would show good miscibility with the selected carriers under certain conditions. Intermolecular hydrogen bonding between the drug and carrier(s) was confirmed by Fourier transform infrared spectroscopy and proton nuclear magnetic resonance spectroscopy. Solid-state characterizations like powder X-ray diffraction, differential scanning calorimetry, and microscopy confirm the amorphous nature of SDs. The addition of the effervescent agent improved the amorphous nature, due to which the solubility and drug release rate was increased. In vitro and ex vivo intestinal absorption studies showed improved flux and permeability than the pure drug, suggesting an enhanced drug delivery. The GLB solubility, dissolution, and stability were greatly enhanced by the SD and ESD technology. Graphical Abstract

Effects of Different Parameters and Co-digestion Options on Anaerobic Digestion of Parboiled Rice Mill Wastewater: a Review - Chilaka Chetan Naveen; Bella Kunnoth; Sridhar Pilli; Polisetty Venkateswara Rao; Rao Y. Surampalli; Tian C. Zhang; Puspendu Bhunia (BioEnergy Research, 2022)

Molecular dynamics and structure-based virtual screening and identification of natural compounds as Wnt signaling modulators: possible therapeutics for Alzheimer’s disease - Suman Manandhar; Runali Sankhe; Keerthi Priya; Gangadhar Hari; Harish Kumar B.; Chetan H. Mehta; Usha Y. Nayak; K. Sreedhara Ranganath Pai (Molecular Diversity, 2022)
Wnt signaling pathway is an evolutionarily conserved pathway responsible for neurogenesis, axon outgrowth, neuronal polarity, synapse formation, and maintenance. Downregulation of Wnt signaling has been found in patients with Alzheimer’s disease (AD). Several experimental approaches to activate Wnt signaling pathway have proven to be beneficial in alleviating AD, which is one of the new therapeutic approaches for AD. The current study focuses on the computational structure-based virtual screening followed by the identification of potential phytomolecules targeting different markers of Wnt signaling like WIF1, DKK1, LRP6, GSK-3β, and acetylcholine esterase. Initially, screening of 1924 compounds from the plant-based library of Zinc database was done for the selected five proteins using docking approach followed by MM-GBSA calculations. The top five hit molecules were identified for each protein. Based on docking score, and binding interactions, the top two hit molecules for each protein were selected as promising molecules for the molecular dynamic (MD) simulation study with the five proteins. Therefore, from this in silico based study, we report that Mangiferin could be a potential molecule targeting Wnt signaling pathway modulating the LRP6 activity, Baicalin for AChE activity, Chebulic acid for DKK1, ZINC103539689 for WIF1, and Morin for GSk-3β protein. However, further validation of the activity is warranted based on in vivo and in vitro experiments for better understanding and strong claim. This study provides an in silico approach for the identification of modulators of the Wnt signaling pathway as a new therapeutic approach for AD. Graphical Abstract

Machine learning for geochemical exploration: classifying metallogenic fertility in arc magmas and insights into porphyry copper deposit formation - Chetan L. Nathwani; Jamie J. Wilkinson; George Fry; Robin N. Armstrong; Daniel J. Smith; Christian Ihlenfeld (Mineralium Deposita, 2022)
A current mineral exploration focus is the development of tools to identify magmatic districts predisposed to host porphyry copper deposits. In this paper, we train and test four, common, supervised machine learning algorithms: logistic regression, support vector machines, artificial neural networks (ANN) and Random Forest to classify metallogenic ‘fertility’ in arc magmas based on whole-rock geochemistry. We outline pre-processing steps that can be used to mitigate against the undesirable characteristics of geochemical data (high multicollinearity, sparsity, missing values, class imbalance and compositional data effects) and therefore produce more meaningful results. We evaluate the classification accuracy of each supervised machine learning technique using a tenfold cross-validation technique and by testing the models on deposits unseen during the training process. This yields 81–83% accuracy for all classifiers, and receiver operating characteristic (ROC) curves have mean area under curve (AUC) scores of 87–89% indicating the probability of ranking a ‘fertile’ rock higher than an ‘unfertile’ rock. By contrast, bivariate classification schemes show much lower performance, demonstrating the value of classifying geochemical data in high dimension space. Principal component analysis suggests that porphyry-fertile magmas fractionate deep in the arc crust, and that calc-alkaline magmas associated with Cu-rich porphyries evolve deeper in the crust than more alkaline magmas linked with Au-rich porphyries. Feature analysis of the machine learning classifiers suggests that the most important parameters associated with fertile magmas are low Mn, high Al, high Sr, high K and listric REE patterns. These signatures further highlight the association of porphyry Cu deposits with hydrous arc magmas that undergo amphibole fractionation in the deep arc crust.

A Three-Tier Approach as a Next-Gen Sustainable Solution for Mitigation of Urban Air Pollution - Chetan Keswani; Tatiana Minkina; Svetlana Sushkova; Saglara Mandzhieva (Anthropocene Science, 2022)

Coexistent Seizures and NREM Parasomnia: A Case Report - Kaustav Kundu; Namrta Kumari; Gaurav Sharma; Chetan Sharma (Sleep and Vigilance, 2022)

ModelOps for enhanced decision-making and governance in emergency control rooms - Kay Lefevre; Chetan Arora; Kevin Lee; Arkady Zaslavsky; Mohamed Reda Bouadjenek; Ali Hassani; Imran Razzak (Environment Systems and Decisions, 2022)
For mission critical (MC) applications such as bushfire emergency management systems (EMS), understanding the current situation as a disaster unfolds is critical to saving lives, infrastructure and the environment. Incident control-room operators manage complex information and systems, especially with the emergence of Big Data. They are increasingly making decisions supported by artificial intelligence (AI) and machine learning (ML) tools for data analysis, prediction and decision-making. As the volume, speed and complexity of information increases due to more frequent fire events, greater availability of myriad IoT sensors, smart devices, satellite data and burgeoning use of social media, the advances in AI and ML that help to manage Big Data and support decision-making are increasingly perceived as “Black Box”. This paper aims to scope the requirements for bushfire EMS to improve Big Data management and governance of AI/ML. An analysis of ModelOps technology, used increasingly in the commercial sector, is undertaken to determine what components might be fit-for-purpose. The result is a novel set of ModelOps features, EMS requirements and an EMS-ModelOps framework that resolves more than 75% of issues whilst being sufficiently generic to apply to other types of mission-critical applications.

Implication of stress behaviour in the rocks exposed along Markhandaya River, with a special emphasis on microstructures and deformation temperature, Gokak, India - Anant G. Pujar; Chetan P. Hanji; Manish S. Dharek; Marularadhya C. Hiremath (Innovative Infrastructure Solutions, 2022)

Emerging Technologies for Non-invasive Monitoring of Treatment Response to Immunotherapy for Brain Tumors - Dimitrios Mathios; Siddhartha Srivastava; Timothy Kim; Chetan Bettegowda; Michael Lim (NeuroMolecular Medicine, 2022)

Influence of Different Nutrient Management Practices and Cropping Systems on Organic Carbon Pools in Typic Ustochrept Soil of Indo-Gangetic Plains in India - Debashis Dutta; A. L. Meena; Amit Kumar; N. Subash; R. P. Mishra; P. C. Ghasal; Jairam Choudhary; Chandra Bhanu; Raghavendra KJ; Chetan Kumar G; Ankur Kumar; Vaibhav Kumar; et al. (Journal of Soil Science and Plant Nutrition, 2022)

The viral phoenix: enhanced infectivity and immunity evasion of SARS-CoV-2 variants - Hosoon Choi; Piyali Chatterjee; Munok Hwang; Eric Lichtfouse; Virender K. Sharma; Chetan Jinadatha (Environmental Chemistry Letters, 2022)

Spatial transcriptomic analysis reveals inflammatory foci defined by senescent cells in the white matter, hippocampi and cortical grey matter in the aged mouse brain - Tamas Kiss; Ádám Nyúl-Tóth; Jordan DelFavero; Priya Balasubramanian; Stefano Tarantini; Janet Faakye; Rafal Gulej; Chetan Ahire; Anna Ungvari; Andriy Yabluchanskiy; Graham Wiley; Lori Garman; et al. (GeroScience, 2022)

Cerebral venous congestion exacerbates cerebral microhemorrhages in mice - Adam Nyul-Toth; Gabor A. Fulop; Stefano Tarantini; Tamas Kiss; Chetan Ahire; Janet A. Faakye; Anna Ungvari; Peter Toth; Attila Toth; Anna Csiszar; Zoltan Ungvari (GeroScience, 2022)

Co-ordinated responses to endogenous and environmental triggers allow a well-timed floral transition in plants - Chetan Kaur; Yong Pyo Lim; Geung-Joo Lee (Plant Biotechnology Reports, 2022)

Potential Inhibitors Targeting Escherichia coli UDP-N-Acetylglucosamine Enolpyruvyl Transferase (MurA): An Overview - Diksha Raina; Chetan Kumar; Vinod Kumar; Inshad Ali Khan; Saurabh Saran (Indian Journal of Microbiology, 2022)

Dual Trichoderma consortium mediated elevation of systemic defense response against early blight in potato - Sumit Kumar; Ram Chandra; Lopamudra Behera; Chetan Keswani; Estibaliz Sansinenea (European Journal of Plant Pathology, 2022)

Extracellular Signal-Regulated Kinase1 (ERK1)-Mediated Phosphorylation of Voltage-Dependent Anion Channel (VDAC) Suppresses its Conductance - Chetan Malik; Shumaila Iqbal Siddiqui; Subhendu Ghosh (The Journal of Membrane Biology, 2022)

A review on various aspects of organic synthesis using Comins’ reagent - Duraipandi Devi Priya; Chetan Lakshman; Selvaraj Mohana Roopan (Molecular Diversity, 2022)

Global footprints of organochlorine pesticides: a pan-global survey - Chetan Keswani; Hagera Dilnashin; Hareram Birla; Partha Roy; Rakesh K. Tyagi; Dheer Singh; Vishnu D. Rajput; Tatiana Minkina; Surya P. Singh (Environmental Geochemistry and Health, 2022)

Metamorphosis of Twin Screw Extruder-Based Granulation Technology: Applications Focusing on Its Impact on Conventional Granulation Technology - Rajat Radhakrishna Rao; Abhijeet Pandey; Aswathi R. Hegde; Vijay Induvadan Kulkarni; Chetan Chincholi; Vinay Rao; Indu Bhushan; Srinivas Mutalik (AAPS PharmSciTech, 2022)
In order to be at pace with the market requirements of solid dosage forms and regulatory standards, a transformation towards systematic processing using continuous manufacturing (CM) and automated model-based control is being thought through for its fundamental advantages over conventional batch manufacturing. CM eliminates the key gaps through the integration of various processes while preserving quality attributes via the use of process analytical technology (PAT). The twin screw extruder (TSE) is one such equipment adopted by the pharmaceutical industry as a substitute for the traditional batch granulation process. Various types of granulation techniques using twin screw extrusion technology have been explored in the article. Furthermore, individual components of a TSE and their conjugation with PAT tools and the advancements and applications in the field of nutraceuticals and nanotechnology have also been discussed. Thus, the future of granulation lies on the shoulders of continuous TSE, where it can be coupled with computational mathematical studies to mitigate its complications.

Apical, sub-apical, and basal explants of industrially exploited marine red alga Gracilaria salicornia exhibited differential response to commercial seaweed-derived plant bio-stimulants - Santlal Jaiswar; Pankaj S. Dawange; Chetan Thanth; Vaibhav A. Mantri (Journal of Applied Phycology, 2021)

Economic Shock and Agri-Sector: Post-COVID-19 Scenario in India - Hagera Dilnashin; Hareram Birla; Vishnu D. Rajput; Chetan Keswani; Surya P. Singh; Tatiana M. Minkina; Saglara S. Mandzhieva (Circular Economy and Sustainability, 2021)

Climate change-induced high-altitude lake: Hydrochemistry and area changes of a moraine-dammed lake in Leh-Ladakh - Himanshu Kaushik; AL. Ramanathan; Mohd Soheb; Monica Sharma Shamurailatpam; Kalyan Biswal; Arindan Mandal; Chetan Singh (Acta Geophysica, 2021)

Clinico-pathological and Molecular Spectrum of Mitochondrial Polymerase γ Mutations in a Cohort from India - Sekar Deepha; Periyasamy Govindaraj; Bindu Parayil Sankaran; Shwetha Chiplunkar; Chetan Kashinkunti; Vandana Nunia; Madhu Nagappa; Sanjib Sinha; Tripti Khanna; Kumarasamy Thangaraj; Arun B. Taly; Narayanappa Gayathri (Journal of Molecular Neuroscience, 2021)

Treatment with the BCL-2/BCL-xL inhibitor senolytic drug ABT263/Navitoclax improves functional hyperemia in aged mice - Stefano Tarantini; Priya Balasubramanian; Jordan Delfavero; Tamas Csipo; Andriy Yabluchanskiy; Tamas Kiss; Ádám Nyúl-Tóth; Peter Mukli; Peter Toth; Chetan Ahire; Anna Ungvari; Zoltan Benyo; et al. (GeroScience, 2021)

Resource use and the impacts of fisheries on two sympatric sea snake species on the west coast of India - Shawn Dsouza; Chetan Rao; Muralidharan Manoharakrishnan; Kartik Shanker (Marine Biology, 2021)

Structurally nanoengineered antimicrobial peptide polymers: design, synthesis and biomedical applications - Ronisha Ramamurthy; Chetan H. Mehta; Usha Y. Nayak (World Journal of Microbiology and Biotechnology, 2021)
Antimicrobial resistance not only increases the contagiousness of infectious diseases but also a threat for the future as it is one of the health care concern around the globe. Conventional antibiotics are unsuccessful in combating chronic infections caused by multidrug-resistant (MDR) bacteria, therefore it is important to design and develop novel strategies to tackle this problems. Among various novel strategies, Structurally Nanoengineered Antimicrobial Peptide Polymers (SNAPPs) have been introduced in recent years to overcome this global health care issue and they are found to be more efficient in their performance. Many facile methods are adapted to synthesize complex SNAPPs with required dimensions and unique functionalities. Their unique characteristics and remarkable properties have been exploited for their immense applications in various fields including biomedicine, targeting therapies, gene delivery, bioimaging, and many more. This review article deals with its background, design, synthesis, mechanism of action, and wider applications in various fields of SNAPPs. Graphic abstract

Hydrogen Sulfide Ameliorates Lipopolysaccharide-Induced Memory Impairment in Mice by Reducing Apoptosis, Oxidative, and Inflammatory Effects - Viplav Kshirsagar; Chetan Thingore; Malvika Gursahani; Nitin Gawali; Archana Juvekar (Neurotoxicity Research, 2021)

Sorption of brilliant green dye using soybean straw-derived biochar: characterization, kinetics, thermodynamics and toxicity studies - Govind Vyavahare; Ranjit Gurav; Ravishankar Patil; Shubham Sutar; Pooja Jadhav; Devashree Patil; Yung-Hun Yang; Jingchun Tang; Chetan Chavan; Sangeeta Kale; Jyoti Jadhav (Environmental Geochemistry and Health, 2021)

RP-HPLC analysis of diterpene lactones in leaves and stem of different species of Andrographis - Dayanand Dalawai; Chetan Aware; Jyoti P. Jadhav; Hosakatte Niranjana Murthy (Natural Product Research, 2021)

Application of a convolutional neural network to improve automated early warning of harmful algal blooms - Darren W. Henrichs; Sílvia Anglès; Chetan C. Gaonkar; Lisa Campbell (Environmental Science and Pollution Research, 2021)

Current understanding of the surface contamination and contact transmission of SARS-CoV-2 in healthcare settings - Hosoon Choi; Piyali Chatterjee; John D. Coppin; Julie A. Martel; Munok Hwang; Chetan Jinadatha; Virender K. Sharma (Environmental Chemistry Letters, 2021)

COVID-19 epidemiologic surveillance using wastewater - Virender K. Sharma; Chetan Jinadatha; Eric Lichtfouse; Etienne Decroly; Jacques van Helden; Hosoon Choi; Piyali Chatterjee (Environmental Chemistry Letters, 2021)

Classical and alternative disinfection strategies to control the COVID-19 virus in healthcare facilities: a review - Hosoon Choi; Piyali Chatterjee; Eric Lichtfouse; Julie A. Martel; Munok Hwang; Chetan Jinadatha; Virender K. Sharma (Environmental Chemistry Letters, 2021)

Sequence and functional analysis of MIR319 promoter homologs from Brassica juncea reveals regulatory diversification and altered expression under stress - Gauri Arora nee Joshi; Chetan Chauhan; Sandip Das (Molecular Genetics and Genomics, 2021)

Measurements of Bicarbonate in Water Containing Ocean-Level Sulfate Using a Simple Multi-Pass Optical Raman System - Chetan Shende; Stuart Farquharson; Duncan Farquharson; Carl Brouillette (Oceans, 2021)
The concentration of dissolved inorganic carbon in the oceans at depths of a few meters to thousands of meters is a critical parameter for understanding global warming. The concentration is both pH dependent and depth dependent. Current analysis that employs pH meters must account for several other parameters, such as salinity, temperature, pressure, and the dissolved carbon’s form, carbon dioxide, bicarbonate, or carbonate. Recently, Raman spectroscopy has been used to measure these forms directly in water at ~1000 ppm, which is unfortunately insufficient for typical ocean concentrations, such as ~115 ppm bicarbonate near the surface. Here, we employed a simple multi-pass optical system, a flat mirror to reflect the laser back through the sample, and a concave mirror opposite the entrance slit that effectively doubled the laser power and the collected Raman photons, respectively. This multi-pass optical Raman system with a 1.5 W, 532 nm laser was used to measure 30 ppm bicarbonate in water that contained 2650 ppm sulfate to simulate ocean water, a bicarbonate concentration well below that near the ocean surface. Furthermore, spectral analysis employed the bicarbonate C=O symmetric stretch at 1360 cm−1 instead of the C–OH stretch at 1015 cm−1 to avoid the intense, overlapping sulfate SO4 symmetric stretch at 985 cm−1. The calculated standard deviation of ~5 ppm for the described approach suggests that accurate measurement of bicarbonate in situ is possible, which has been, heretofore, either calculated based on pH or measured in a lab.

Amelioration of oxidative stress and neuroinflammation in lipopolysaccharide-induced memory impairment using Rosmarinic acid in mice - Chetan Thingore; Viplav Kshirsagar; Archana Juvekar (Metabolic Brain Disease, 2021)

The place beyond the pines: bioeconomy delivering sustainable green growth A book review on The Bioeconomy: Delivering Sustainable Green Growth by Davide Viaggi, CABI, UK, 2018, 224 pp., ISBN: 9781786392756 - Chetan Keswani; Hareram Birla; Hagera Dilnashin (Environment, Development and Sustainability, 2021)

From long-lived batholith construction to giant porphyry copper deposit formation: petrological and zircon chemical evolution of the Quellaveco District, Southern Peru - Chetan L. Nathwani; Adam T. Simmons; Simon J. E. Large; Jamie J. Wilkinson; Yannick Buret; Christian Ihlenfeld (Contributions to Mineralogy and Petrology, 2021)
Porphyry Cu ore deposits are a rare product of arc magmatism that often form spatiotemporal clusters in magmatic arcs. The petrogenetic evolution of igneous rocks that cover the temporal window prior to and during porphyry Cu deposit formation may provide critical insights into magmatic processes that are key in generating these systems. This study documents the magmatic evolution of the Palaeocene–Eocene Yarabamba Batholith, Southern Peru, that was incrementally assembled between ~ 67 and ~ 59 Ma and hosts three, nearly contemporaneous, giant porphyry Cu–Mo deposits that formed at 57–54 Ma (Quellaveco, Toquepala and Cuajone). Whole-rock geochemistry, U–Pb geochronology and zircon trace element chemistry are reported from Yarabamba rocks that span the duration of plutonic activity, and from six porphyry intrusions at Quellaveco that bracket mineralisation. A change in whole-rock chemistry in Yarabamba intrusive rocks to high Sr/Y, high La/Yb and high Eu/Eu* is observed at ~ 60 Ma which is broadly coincident with a change in vector of the converging Nazca plate and the onset of regional compression and crustal thickening during the first stage of the Incaic orogeny. The geochemical changes are interpreted to reflect a deepening of the locus of lower crustal magma evolution in which amphibole ± garnet are stabilised as early and abundant fractionating phases and plagioclase is suppressed. Zircons in these rocks show a marked change towards higher Eu/Eu* (> 0.3) and lower Ti (< 9 ppm) compositions after ~ 60 Ma. Numerical modelling of melt Eu systematics and zircon-melt partitioning indicates that the time series of zircon Eu/Eu* in these rocks can be explained by a transition from shallower, plagioclase-dominated fractionation to high-pressure amphibole-dominated fractionation at deep crustal levels from ~ 60 Ma. Our modelling suggests that any redox effects on zircon Eu/Eu* are subordinate compared to changes in melt composition controlled by the fractionating mineral assemblage. We suggest that growth and intermittent recharge of the lower crustal magma reservoir from ~ 60 Ma produced a significant volume of hydrous and metallogenically fertile residual melt which ascended to the upper crust and eventually generated the three giant porphyry Cu–Mo deposits at Quellaveco, Toquepala and Cuajone from ~ 57 Ma. Our study highlights the importance of high-pressure magma differentiation fostered by strongly compressive tectonic regimes in generating world-class porphyry Cu deposits.

Exploring assumptions in crop breeding for climate resilience: opportunities and principles for integrating climate model projections - Stephen Whitfield; Sarah Chapman; Marcelin Tonye Mahop; Chetan Deva; Kennedy Masamba; Andekelile Mwamahonje (Climatic Change, 2021)
Crop breeding for resilience to changing climates is a key area of investment in African agricultural development, but proactively breeding for uncertain future climates is challenging. In this paper, we characterise efforts to breed new varieties of crops for climate resilience in southern Africa and evaluate the extent to which climate model projections currently inform crop breeding activity. Based on a survey of seed system actors, we find that the prioritisation of crops and traits is only informed to a limited extent by modelled projections. We use an ensemble of CORDEX models for mid and end of century for southern Africa to test some of the assumptions that underpin current breeding activity, particularly associated with breeding for reduced durations and drought tolerance in maize, and demonstrate some of the ways in which such projections can help to inform breeding priorities and agenda setting (e.g. through the case of assessing cassava toxicity risk). Based on these examples, we propose five potential applications of climate models in informing breeding priorities. Furthermore, after unpacking the sources of uncertainty within the presented model projections, we discuss general principles for the appropriate use of climate model information in crop breeding.

Insulin resistance: a connecting link between Alzheimer’s disease and metabolic disorder - Viplav Kshirsagar; Chetan Thingore; Archana Juvekar (Metabolic Brain Disease, 2021)

Cyanobacterial biofertilizer’s successful journey from rural technology to commercial enterprise: an Indian perspective - Neeru Bhooshan; Amarjeet Singh; Akriti Sharma; Chetan Verma; Anjani Kumar; Sunil Pabbi (Journal of Applied Phycology, 2020)

Metal toxicity and natural antidotes: prevention is better than cure - Chetan Rajak; Neelu Singh; Poonam Parashar (Environmental Science and Pollution Research, 2020)

How a typical West African day in the future-climate compares with current-climate conditions in a convection-permitting and parameterised convection climate model - Rory G. J. Fitzpatrick; Douglas J. Parker; John H. Marsham; David P. Rowell; Lawrence S. Jackson; Declan Finney; Chetan Deva; Simon Tucker; Rachael Stratton (Climatic Change, 2020)
Current-climate precipitation and temperature extremes have been identified by decision makers in West Africa as among the more impactful weather events causing lasting socioeconomic damage. In this article, we use a plausible future-climate scenario (RCP8.5) for the end of the twenty-first century to explore the relative commonness of such extremes under global warming. The analysis presented considers what a typical day in the future climate will feel like relative to current extrema. Across much of West Africa, we see that the typical future-climate day has maximum and minimum temperatures greater than 99.5% of currently experienced values. This finding exists for most months but is particularly pronounced during the Boreal spring and summer. The typical future precipitation event has a daily rainfall rate greater than 95% of current storms. These findings exist in both a future scenario model run with and without parameterised convection, and for many of the Coupled Model Inter-comparison Project version 5 ensemble members. Additionally, agronomic monsoon onset is projected to occur later and have greater inter-annual variability in the future. Our findings suggest far more extreme conditions in future climate over West Africa. The projected changes in temperature and precipitation could have serious socioeconomic implications, stressing the need for effective mitigation given the potential lack of adaptation pathways available to decision makers.

Nutrient Deprivation Mobilizes the Production of Unique Tocopherols as a Stress-Promoting Response in a New Indigenous Isolate Monoraphidium sp. - Rabinder Singh; Chetan Paliwal; Asha A. Nesamma; Alka Narula; Pannaga P. Jutur (Frontiers in Marine Science, 2020)

Mechanistic Insights of Astrocyte-Mediated Hyperactive Autophagy and Loss of Motor Neuron Function in SOD1L39R Linked Amyotrophic Lateral Sclerosis - Chetan Singh Rajpurohit; Vivek Kumar; Arquimedes Cheffer; Danyllo Oliveira; Henning Ulrich; Oswaldo Keith Okamoto; Mayana Zatz; Uzair Ahmad Ansari; Vinay Kumar Khanna; Aditya Bhushan Pant (Molecular Neurobiology, 2020)

Modulation of the mitochondrial voltage-dependent anion channel (VDAC) by hydrogen peroxide and its recovery by curcumin - Chetan Malik; Subhendu Ghosh (European Biophysics Journal, 2020)

Antimicrobial peptide polymers: no escape to ESKAPE pathogens—a review - Songhita Mukhopadhyay; A. S. Bharath Prasad; Chetan H. Mehta; Usha Y. Nayak (World Journal of Microbiology and Biotechnology, 2020)
Antimicrobial resistance (AMR) is one of the significant clinical challenges and also an emerging area of concern arising from nosocomial infections of ESKAPE pathogens, which has been on the rise in both the developed and developing countries alike . These pathogens/superbugs can undergo rapid mutagenesis, which helps them to generate resistance against antimicrobials in addition to the patient’s non-adherence to the antibiotic regimen. Sticking to the idea of a ‘one-size-fits-all’ approach has led to the inappropriate administration of antibiotics resulting in augmentation of antimicrobial resistance. Antimicrobial peptides (AMPs) are the natural host defense peptides that have gained attention in the field of AMR, and recently, synthetic AMPs are well studied to overcome the drawbacks of natural counterparts. This review deals with the novel techniques utilizing the bacteriolytic activity of natural AMPs. The effective localization of these peptides onto the negatively charged bacterial surface by using nanocarriers and structurally nanoengineered antimicrobial peptide polymers (SNAPPs) owing to its smaller size and better antimicrobial activity is also described here. Graphic abstract

Regulation of Single-Channel Conductance of Voltage-Dependent Anion Channel by Mercuric Chloride in a Planar Lipid Bilayer - Chetan Malik; Subhendu Ghosh (The Journal of Membrane Biology, 2020)

Purification and biochemical characterization of a novel secretory dipeptidyl peptidase IV from porcine serum - Divya Kumar; Vivek K. Hamse; K. N. Neema; Priya Babu Shubha; D. M. Chetan; Nanjunda Swamy Shivananju (Molecular and Cellular Biochemistry, 2020)

In vitro and in vivo evaluation of gentamicin sulphate-loaded PLGA nanoparticle-based film for the treatment of surgical site infection - Chetan Dhal; Renuka Mishra (Drug Delivery and Translational Research, 2020)

Mitigation of Elasmobranch Bycatch in Trawlers: A Case Study in Indian Fisheries - Trisha Gupta; Hollie Booth; William Arlidge; Chetan Rao; Muralidharan Manoharakrishnan; Naveen Namboothri; Kartik Shanker; E. J. Milner-Gulland (Frontiers in Marine Science, 2020)

Environmental chemistry is most relevant to study coronavirus pandemics - Virender K. Sharma; Chetan Jinadatha; Eric Lichtfouse (Environmental Chemistry Letters, 2020)

A new trend function-based regression kriging for spatial modeling of groundwater hydraulic heads under the sparse distribution of measurement sites - S. Mohanasundaram; Parmeshwar Udmale; Sangam Shrestha; Triambak Baghel; Smit Chetan Doshi; Balaji Narasimhan; G. Suresh Kumar (Acta Geophysica, 2020)

Species detection and delineation in the marine planktonic diatoms Chaetoceros and Bacteriastrum through metabarcoding: making biological sense of haplotype diversity - Chetan C. Gaonkar; Roberta Piredda; Diana Sarno; Adriana Zingone; Marina Montresor; Wiebe H. C. F. Kooistra (Environmental Microbiology, 2020)
Summary High‐throughput sequencing (HTS) metabarcoding is commonly applied to assess phytoplankton diversity. Usually, haplotypes are grouped into operational taxonomic units (OTUs) through clustering, whereby the resulting number of OTUs depends on chosen similarity thresholds. We applied, instead, a phylogenetic approach to infer taxa among 18S rDNA V4‐metabarcode haplotypes gathered from 48 time‐series samples using the marine planktonic diatoms Chaetoceros and Bacteriastrum as test case. The 73 recovered taxa comprised both solitary haplotypes and polytomies, the latter composed each of a highly abundant, dominant haplotype and one to several minor, peripheral haplotypes. The solitary and dominant haplotypes usually matched reference sequences, enabling species assignation of taxa. We hypothesise that the super‐abundance of reads in dominant haplotypes results from the homogenization effect of concerted evolution. Reads of populous peripheral haplotypes and dominant haplotypes show comparable distribution patterns over the sample dates, suggesting that they are part of the same population. Many taxa revealed marked seasonality, with closely related ones generally showing distinct periodicity, whereas others occur year‐round. Phylogenies inferred from metabarcode haplotypes enable delineation of biologically meaningful taxa, whereas OTUs resulting from clustering algorithms often deviate markedly from such taxa.

Single-cell RNA sequencing identifies senescent cerebromicrovascular endothelial cells in the aged mouse brain - Tamas Kiss; Ádám Nyúl-Tóth; Priya Balasubramanian; Stefano Tarantini; Chetan Ahire; Jordan DelFavero; Andriy Yabluchanskiy; Tamas Csipo; Eszter Farkas; Graham Wiley; Lori Garman; Anna Csiszar; et al. (GeroScience, 2020)

Nicotinamide mononucleotide (NMN) supplementation promotes neurovascular rejuvenation in aged mice: transcriptional footprint of SIRT1 activation, mitochondrial protection, anti-inflammatory, and anti-apoptotic effects - Tamas Kiss; Ádám Nyúl-Tóth; Priya Balasubramanian; Stefano Tarantini; Chetan Ahire; Andriy Yabluchanskiy; Tamas Csipo; Eszter Farkas; Jonathan D. Wren; Lori Garman; Anna Csiszar; Zoltan Ungvari (GeroScience, 2020)

Pharmacological or genetic depletion of senescent astrocytes prevents whole brain irradiation–induced impairment of neurovascular coupling responses protecting cognitive function in mice - Andriy Yabluchanskiy; Stefano Tarantini; Priya Balasubramanian; Tamas Kiss; Tamas Csipo; Gábor A. Fülöp; Agnes Lipecz; Chetan Ahire; Jordan DelFavero; Adam Nyul-Toth; William E. Sonntag; Michal L. Schwartzman; et al. (GeroScience, 2020)

Quinidine partially blocks mitochondrial voltage-dependent anion channel (VDAC) - Chetan Malik; Subhendu Ghosh (European Biophysics Journal, 2020)

Microbial degradation of poultry feather biomass in a constructed bioreactor and application of hydrolysate as bioenhancer to vegetable crops - Ranjit Gurav; Virdhaval Nalavade; Chetan Aware; Govind Vyavahare; Shashi Kant Bhatia; Yung-Hun Yang; Vishwas Bapat; Jyoti Jadhav (Environmental Science and Pollution Research, 2020)

Seed and seedling establishment in abandoned tea plantations role of ecological and edaphic factors, southern Western Ghats, India - H. C. Chetan; R. Ganesan; T. Ganesh (Tropical Ecology, 2019)

RP-HPLC Analysis of Anti-Parkinson’s Drug l-DOPA Content in Mucuna Species from Indian Subcontinent - Ravishankar Patil; Chetan Aware; Swaroopsingh Gaikwad; Manisha Rajebhosale; Vishwas Bapat; Shrirang Yadav; Jyoti Jadhav (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Assessment of Human Health Risk Associated with High Groundwater Fluoride Intake in Southern Districts of Punjab, India - Chetan P. S. Ahada; Surindra Suthar (Exposure and Health, 2019)

Quality Control in Huntington’s Disease: a Therapeutic Target - Sachchida Nand Rai; Brijesh Kumar Singh; Aaina Singh Rathore; Walia Zahra; Chetan Keswani; Hareram Birla; Saumitra Sen Singh; Hagera Dilnashin; Surya Pratap Singh (Neurotoxicity Research, 2019)

Anti-inflammatory Activity of Ursolic Acid in MPTP-Induced Parkinsonian Mouse Model - Sachchida Nand Rai; Walia Zahra; Saumitra Sen Singh; Hareram Birla; Chetan Keswani; Hagera Dilnashin; Aaina Singh Rathore; Rajan Singh; Rakesh K. Singh; Surya Pratap Singh (Neurotoxicity Research, 2019)

Cerebral venous congestion promotes blood-brain barrier disruption and neuroinflammation, impairing cognitive function in mice - Gabor A. Fulop; Chetan Ahire; Tamas Csipo; Stefano Tarantini; Tamas Kiss; Priya Balasubramanian; Andriy Yabluchanskiy; Eszter Farkas; Attila Toth; Ádám Nyúl-Tóth; Peter Toth; Anna Csiszar; et al. (GeroScience, 2019)

Treatment with the poly(ADP-ribose) polymerase inhibitor PJ-34 improves cerebromicrovascular endothelial function, neurovascular coupling responses and cognitive performance in aged mice, supporting the NAD+ depletion hypothesis of neurovascular aging - Stefano Tarantini; Andriy Yabluchanskiy; Tamas Csipo; Gabor Fulop; Tamas Kiss; Priya Balasubramanian; Jordan DelFavero; Chetan Ahire; Anna Ungvari; Ádám Nyúl-Tóth; Eszter Farkas; Zoltan Benyo; et al. (GeroScience, 2019)

Conservation of molecular and cellular phenotypes of invariant NKT cells between humans and non-human primates - Krystle K. Q. Yu; Damien B. Wilburn; Joshua A. Hackney; Patricia A. Darrah; Kathryn E. Foulds; Charlotte A. James; Malisa T. Smith; Lichen Jing; Robert A. Seder; Mario Roederer; David M. Koelle; Willie J. Swanson; et al. (Immunogenetics, 2019)

Design, synthesis and biological evaluation of alantolactone derivatives as potential anti-inflammatory agents - Chetan Kumar; Anil Kumar; Yedukondalu Nalli; Waseem I. Lone; Naresh K. Satti; M. K. Verma; Zabeer Ahmed; Asif Ali (Medicinal Chemistry Research, 2019)

Geology of the Renard 65 kimberlite pipe, Québec, Canada - Matthew Gaudet; Maya Kopylova; Colleen Muntener; Vlad Zhuk; Chetan Nathwani (Mineralogy and Petrology, 2018)

Association of CILP, COL9A2 and MMP3 Gene Polymorphisms with Lumbar Disc Degeneration in an Indian Population - Harshitha S.M.; Sibin M.K.; Chetan G.K.; Dhananjaya I. Bhat (Journal of Molecular Neuroscience, 2018)

Groundwater nitrate contamination and associated human health risk assessment in southern districts of Punjab, India - Chetan P. S. Ahada; Surindra Suthar (Environmental Science and Pollution Research, 2018)

A GIS based DRASTIC model for assessing aquifer vulnerability in Southern Punjab, India - Chetan P. S. Ahada; Surindra Suthar (Modeling Earth Systems and Environment, 2018)

A Diagnostic System for Detection of Atrial and Ventricular Arrhythmia Episodes from Electrocardiogram - Apoorv Chetan; Rajesh K. Tripathy; Samarendra Dandapat (Journal of Medical and Biological Engineering, 2018)

A Science and Risk-Based Pragmatic Methodology for Blend and Content Uniformity Assessment - Naheed Sayeed-Desta; Ajay Babu Pazhayattil; Jordan Collins; Chetan Doshi (AAPS PharmSciTech, 2018)

Differentiation of bovine herpesvirus1 subtypes based on UL0.5 gene sequencing - Muthannan A. Ramakrishnan; Chetan Y. Pundkar; Arfa Fayaz; S. ChandraSekar; R. Mageswary; Deenanath Ashokkumar; Rukhsana Bano; Dhanavelu Muthuchelvan; Sukdeb Nandi; V. K. Gupta (VirusDisease, 2018)

Perspectives on medicinal properties of natural phenolic monoterpenoids and their hybrids - Jamatsing D. Rajput; Suresh D. Bagul; Umesh D. Pete; Chetan M. Zade; Subhash B. Padhye; Ratnamala S. Bendre (Molecular Diversity, 2018)

Assessing groundwater hydrochemistry of Malwa Punjab, India - Chetan P. S. Ahada; Surindra Suthar (Arabian Journal of Geosciences, 2018)

Effect of rs11614913 Polymorphism on Mature miR196a2 Expression and its Target Gene HOXC8 Expression in Human Glioma - M K Sibin; S M Harshitha; K V L Narasingarao; I Bhat Dhananjaya; P Shukla Dhaval; G K Chetan (Journal of Molecular Neuroscience, 2017)

Growth medium standardization and thermotolerance study of the freshwater microalga Acutodesmus dimorphus—a potential strain for biofuel production - Kaumeel Chokshi; Imran Pancha; Rahulkumar Maurya; Chetan Paliwal; Tonmoy Ghosh; Arup Ghosh; Sandhya Mishra (Journal of Applied Phycology, 2016)

Synthesis and biological evaluation of some functionalized 1H-1,2,3-triazole tethered pyrazolo[3,4-b]pyridin-6(7H)-ones as antimicrobial and apoptosis inducing agents - Jayant Sindhu; Harjinder Singh; J. M. Khurana; Jitender Kumar Bhardwaj; Priyanka Saraf; Chetan Sharma (Medicinal Chemistry Research, 2016)

Application of aptamers in diagnostics, drug-delivery and imaging - Chetan Chandola; Sheetal Kalme; Marco G Casteleijn; Arto Urtti; Muniasamy Neerathilingam (Journal of Biosciences, 2016)

When is a forest a forest? Forest concepts and definitions in the era of forest and landscape restoration - Robin L. Chazdon; Pedro H. S. Brancalion; Lars Laestadius; Aoife Bennett-Curry; Kathleen Buckingham; Chetan Kumar; Julian Moll-Rocek; Ima Célia Guimarães Vieira; Sarah Jane Wilson (Ambio, 2016)

Cyanobacterial Pigments as Natural Anti-Hyperglycemic Agents: An In vitro Study - Tonmoy Ghosh; Khushbu Bhayani; Chetan Paliwal; Rahulkumar Maurya; Kaumeel Chokshi; Imran Pancha; Sandhya Mishra (Frontiers in Marine Science, 2016)

Taste Masking of Griseofulvin and Caffeine Anhydrous Using Kleptose Linecaps DE17 by Hot Melt Extrusion - Abhishek Juluri; Carmen Popescu; Leon Zhou; Reena N. Murthy; Vanaja K. Gowda; Chetan Kumar P; Manjeet B. Pimparade; Michael A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2016)

CD133 and BMI1 expressions and its prognostic role in primary glioblastoma - M. K. SIBIN; C. H. LAVANYA; DHANANJAYA I. BHAT; NARASINGA RAO; N. GEETHASHREE; W. VIBHUTI; G. K. CHETAN (Journal of Genetics, 2015)

Plantlet formation via somatic embryogenesis and LC ESI Q-TOF MS determination of secondary metabolites in Butea monosperma (Lam.) Kuntze - Chetan Sharma; Tejaswita Kumari; Garima Pant; Vikas Bajpai; Mukesh Srivastava; Kalyan Mitra; Brijesh Kumar; K. R. Arya (Acta Physiologiae Plantarum, 2015)

Environmental pollutants leading to carcinogenesis: process of natural selection of human cells due to chronic inflammation and sustained stress environment - H. N. Venkatesh; M. Jeru Manoj; D. Ghosh; G. K. Chetan (International Journal of Environmental Science and Technology, 2015)

Modified Hargreaves Equation for Accurate Estimation of Evapotranspiration of Diverse Climate Locations in India - Jignesh Patel; Himanshukumar Patel; Chetan Bhatt (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Design and Optimization of Curcumin–HPβCD Bioadhesive Vaginal Tablets by 23 Factorial Design: In Vitro and In Vivo Evaluation - Umme Hani; H. G. Shivakumar; Atul Srivastava; Nawaz Mahammed; Shailesh Thirumaleshwar; Naga Sravan kumar Varma; Rudra Vaghela; Chetan G. Shinde; M. P. Gowrav (Journal of Pharmaceutical Innovation, 2015)

Molecules support morphology: species status of South Indian populations of the widely distributed Hanuman langur - N. C. Ashalakshmi; K. S. Chetan Nag; K. Praveen Karanth (Conservation Genetics, 2015)

Evaluation of 1-(2-deoxy-2-fluoro-1-d-arabinofuranosyl)-5-iodouracil (FIAU) as an ex vivo bacterial detection agent - David Tung; Gary DeCrescenzo; Dean Welsch; Peter H. Cheung; Chetan Bettegowda; Saurabh Saha (World Journal of Microbiology and Biotechnology, 2014)

Chemoselective N-benzylation of 2-thiohydantoins and 2-thiobarbituric acids catalyzed by PEG-stabilized Ni nanoparticles and their anti-microbial activities - Sneha; Jitender M. Khurana; Chetan Sharma; K. R. Aneja (Medicinal Chemistry Research, 2014)

3D QSAR study of 4H-chromen-1,2,3,4-tetrahydropyrimidine-5-carboxylate derivatives as potential anti-mycobacterial agents - Paresh Patel; Chetan Chintha; Manjunath Ghate; Hardik Bhatt; Vivek K. Vyas (Medicinal Chemistry Research, 2014)

Rapid detection of bovine herpesvirus 1 in bovine semen by loop-mediated isothermal amplification (LAMP) assay - Sachin S. Pawar; Chetan D. Meshram; Niraj K. Singh; Arvind A. Sonwane; Mohini Saini; Sunil S. Rautmare; Dushyant M. Muglikar; B. P. Mishra; Praveen K. Gupta (Archives of Virology, 2014)

Homology modeling, binding site identification, and docking study of human β-arrestin: an adaptor protein involved in apoptosis - Chetan Chintha; Nirzari Gupta; Manjunath Ghate; Vivek K. Vyas (Medicinal Chemistry Research, 2014)

XIAP inhibitor and antiestrogen embelin abrogates metastasis and augments apoptosis in estrogen receptor positive human breast adenocarcinoma cell line MCF-7 - K. R. Sumalatha; G. Abiramasundari; G. K. Chetan; T. Divya; G. Sudhandiran; M. Sreepriya (Molecular Biology Reports, 2014)

Benzenesulfonamide bearing pyrazolylpyrazolines: synthesis and evaluation as anti-inflammatory–antimicrobial agents - Pawan Kumar; Navneet Chandak; Pawan Kaushik; Chetan Sharma; Dhirender Kaushik; Kamal R. Aneja; Pawan K. Sharma (Medicinal Chemistry Research, 2014)

Schiff’s base derivatives bearing 2-thiophenoxyquinoline nucleus as new antibacterial agents - Jigar A. Makawana; Chetan B. Sangani; Shashikant B. Teraiya; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Exploration of antimicrobial potential of pyrazolo[3,4-b]pyridine scaffold bearing benzenesulfonamide and trifluoromethyl moieties - Navneet Chandak; Satish Kumar; Pawan Kumar; Chetan Sharma; Kamal R. Aneja; Pawan K. Sharma (Medicinal Chemistry Research, 2013)

Evaluation of single and dual siRNAs targeting rabies virus glycoprotein and nucleoprotein genes for inhibition of virus multiplication in vitro - Chetan D. Meshram; Niraj K. Singh; Arvind A. Sonwane; Sachin S. Pawar; B. P. Mishra; V. K. Chaturvedi; Mohini Saini; R. P. Singh; Praveen K. Gupta (Archives of Virology, 2013)

Synthesis and evaluation of antibacterial and antifungal activities of new (Z)-3-bromo-4-(1,3-diaryl-1H-pyrazol-4-yl)but-3-en-2-ones and 4-(3-methyl-1-phenyl-1H-pyrazol-5-yl)-1,3-diaryl-1H-pyrazoles - Rashmi Pundeer; Sushma; Vijay Kiran; Chetan Sharma; K. R. Aneja; Om Prakash (Medicinal Chemistry Research, 2013)

Microwave-assisted synthesis of novel 4H-chromene derivatives bearing 2-aryloxyquinoline and their antimicrobial activity assessment - Chetan B. Sangani; Nimesh M. Shah; Manish P. Patel; Ranjan G. Patel (Medicinal Chemistry Research, 2013)

Barnacle larval transport in the Mandovi–Zuari estuarine system, central west coast of India - Grinson George; Dattesh V. Desai; Chetan A. Gaonkar; V. M. Aboobacker; P. Vethamony; Arga Chandrashekar Anil (Journal of Oceanography, 2013)

Degradation of barnacle nauplii: implications to chitin regulation in the marine environment - Lidita Khandeparker; Chetan C. Gaonkar; Dattesh V. Desai (Biologia, 2013)

Microwave-assisted synthesis of pyrido[1,2-a]benzimidazole derivatives of β-aryloxyquinoline and their antimicrobial and antituberculosis activities - Chetan B. Sangani; Hardik H. Jardosh; Manish P. Patel; Ranjan G. Patel (Medicinal Chemistry Research, 2013)

Streamflow Modeling in a Highly Managed Mountainous Glacier Watershed Using SWAT: The Upper Rhone River Watershed Case in Switzerland - Kazi Rahman; Chetan Maringanti; Martin Beniston; Florian Widmer; Karim Abbaspour; Anthony Lehmann (Water Resources Management, 2013)

α,α-Dibromoacetophenones mediated synthesis of some new 7H-7-alkoxy-3-alkyl/phenyl-6-aryl-s-triazolo[3,4-b][1,3,4]thiadiazines and their antimicrobial evaluation - Rashmi Pundeer; Vijay Kiran; Richa Prakash; Sushma; Subhash C. Bhatia; Chetan Sharma; Kamal R. Aneja (Medicinal Chemistry Research, 2012)

Synthesis and biological evaluation of some pyrazole derivatives as anti-inflammatory–antibacterial agents - Pawan Kumar; Navneet Chandak; Pawan Kaushik; Chetan Sharma; Dhirender Kaushik; Kamal R. Aneja; Pawan K. Sharma (Medicinal Chemistry Research, 2012)

Synthesis and antimicrobial activity of 5-((3-aryl-1-phenyl-1H-pyrazol-4-yl)methylene)thiazolidine-2,4-diones - Om Prakash; Deepak K. Aneja; Poonam Lohan; Khalid Hussain; Sanjiv Arora; Chetan Sharma; Kamal R. Aneja (Medicinal Chemistry Research, 2012)

Synthesis of 1-(4-aminosulfonylphenyl)-3,5-diarylpyrazoline derivatives as potent antiinflammatory and antimicrobial agents - Pawan K. Sharma; Satish Kumar; Pawan Kumar; Pawan Kaushik; Chetan Sharma; Dhirender Kaushik; Kamal R. Aneja (Medicinal Chemistry Research, 2012)

Synthesis, spectroscopic, thermal and antimicrobial studies of Co(II), Ni(II), Cu(II) and Zn(II) complexes with Schiff base derived from 4-amino-3-mercapto-6-methyl-5-oxo-1,2,4-triazine - Kiran Singh; Yogender Kumar; Parvesh Puri; Chetan Sharma; K. R. Aneja (Medicinal Chemistry Research, 2012)

Synthesis and antimicrobial activities of some new 5-((3-(aryl)-1-phenyl-1H-pyrazol-4-yl)methylene)-3-phenylthiazolidine-2,4-diones - Om Prakash; Deepak Kumar Aneja; Sanjiv Arora; Chetan Sharma; K. R. Aneja (Medicinal Chemistry Research, 2012)

Application of a Multi-Objective Optimization Method to Provide Least Cost Alternatives for NPS Pollution Control - Chetan Maringanti; Indrajeet Chaubey; Mazdak Arabi; Bernard Engel (Environmental Management, 2011)

Taxonomic Implications of a Field Study of Morphotypes of Hanuman Langurs (Semnopithecus entellus) in Peninsular India - K. S. Chetan Nag; P. Pramod; K. Praveen Karanth (International Journal of Primatology, 2011)

Studies on water quality of Sutlej River around Ludhiana with reference to physicochemical parameters - R. Jindal; Chetan Sharma (Environmental Monitoring and Assessment, 2011)

Changes in the abundance and composition of zooplankton from the ports of Mumbai, India - Chetan A. Gaonkar; Venkat Krishnamurthy; Arga Chandrashekar Anil (Environmental Monitoring and Assessment, 2010)

Intense White Luminescence from Combustion Synthesized Ca12Al14O33: Yb3+/Yb2+ Single Phase Phosphor - Chetan Joshi; K. Kumar; S. B. Rai (Journal of Fluorescence, 2010)

Best management practices for corporate, academic and governmental transfer of sustainable technologies to developing countries - Gilbert L. Rochon; Dev Niyogi; Souleymane Fall; Joseph E. Quansah; Larry Biehl; Bereket Araya; Chetan Maringanti; Angel Torres Valcarcel; Lova Rakotomalala; Hildred S. Rochon; Bertin Hilaire Mbongo; Thierno Thiam (Clean Technologies and Environmental Policy, 2010)

Salmonella brain abscess in a patient on chronic azathioprine therapy for myasthenia gravis: report of an unusual case and review of literature in the postantibiotic era - Chetan R Soni; Gyanendra Kumar; Pradeep C Bollu; Pradeep Sahota; N. Scott Litofsky (Journal of NeuroVirology, 2010)

Community-Based Forest Enterprises in Nepal: An Analysis of Their Role in Increasing Income Benefits to the Poor - Bishnu Hari Pandit; Adrian Albano; Chetan Kumar (Small-scale Forestry, 2009)

Establishment and characterization of a new Aedes aegypti (L.) (Diptera: Culicidae) cell line with special emphasis on virus susceptibility - A. B. Sudeep; Deepti Parashar; Ramesh S. Jadi; Atanu Basu; Chetan Mokashi; Vidya A. Arankalle; Akhilesh C. Mishra (In Vitro Cellular & Developmental Biology - Animal, 2009)

Colon Specific Delivery of Indomethacin: Effect of Incorporating pH Sensitive Polymers in Xanthan Gum Matrix Bases - Laila F. A. Asghar; Chetan B. Chure; Sajeev Chandran (AAPS PharmSciTech, 2009)

Monitoring of High-shear Granulation using Acoustic Emission: Predicting Granule Properties - Michelle K. Papp; Chetan P. Pujara; Rodolfo Pinal (Journal of Pharmaceutical Innovation, 2008)

Acid treatment of melanoma cells selects for invasive phenotypes - Raymond E. Moellering; Kvar C. Black; Chetan Krishnamurty; Brenda K. Baggett; Phillip Stafford; Matthew Rain; Robert A. Gatenby; Robert J. Gillies (Clinical & Experimental Metastasis, 2008)

Bioaccumulation of Heavy Metals by Green Algae - Hiren Doshi; Chetan Seth; Arabinda Ray; I. L. Kothari (Current Microbiology, 2008)

Improvement in Yield and Purity of a Recombinant Malaria Vaccine Candidate Based on the Receptor-Binding Domain of Plasmodium vivax Duffy Binding Protein by Codon Optimization - Syed Shams Yazdani; Ahmad Rushdi Shakri; Priyabrata Pattnaik; M. Moshahid A. Rizvi; Chetan E. Chitnis (Biotechnology Letters, 2006)

A high cell density fermentation strategy to produce recombinant malarial antigen in E. coli - Syed Shams Yazdani; Ahmad Rushdi Shakri; Chetan E. Chitnis (Biotechnology Letters, 2004)

A new paradigm for R&D in water resources engineering - Chetan Pandit (Irrigation and Drainage, 2003)
The technology in water resources engineering (WRE) seems to be stagnant. No new technology of any significance has emerged for quite some time now and there seems to be none in the pipeline. In the WRE sector, R&D does not generate the same level of excitement and challenges that it does in other sectors. Shortage of funds does not seem to be the reason for this disappointing performance of R&D. The main problems are: WRE R&D has very little potential for patents, Intellectual Property Rights (IPR) and profit and therefore the private sector does not take any interest in R&D in WRE. Most of the research pursued by the universities is too theoretical. There is very little applied research. There is a marked lack of creativity and inspiring ideas for R&D. There are neither any “technology dreamers” nor any dreams. Users are not being involved in the planning. The time is running out for R&D managers in WRE. The vision plans of most governments incorporate a set of measurable performance targets to be achieved in a stipulated time frame. Many of the targets are less than 10 years away. Therefore, if R&D is to be of any assistance in achieving the targets set for 2010, then that R&D must start now, not next year. The present approach to R&D has not produced desired results and, therefore, it must be changed immediately. The paper proposes a new approach to provide an impetus to R&D in the WRE sector. Copyright © 2003 John Wiley & Sons, Ltd.

Studies on the antiperoxide and antihaemolytic action of polyamines using human erythrocytes - Chethana Chetan; Ashok Prabhu; Vivian D'Souza; Shrinivas B. Rao (Indian Journal of Clinical Biochemistry, 2000)